Image forming apparatus, and image forming method
Patent Information
- Application Number
- JP2023128182
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
Smart Images

Figure 2025023760000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an image forming apparatus and an image forming method. [Background technology]
[0002] In electrophotographic image forming apparatuses (copying machines, facsimiles, printers, etc.), a toner image formed on the surface of an image carrier such as a photoconductor is transferred to the surface of a recording medium and fixed on the recording medium to form an image. A cleaning blade is used to clean the outer peripheral surface of the image carrier.
[0003] For example, Patent Document 1 discloses "a cleaning blade for cleaning residual powder and other foreign matter, the cleaning blade comprising a blade body whose edge portion can be pressed against a surface on which the foreign matter remains, and a lubricating layer provided on at least the surface of the blade body facing the surface on which the foreign matter remains, the blade body being set in a pressed state in which the edge portion and the lubricating layer are simultaneously pressed against the surface on which the foreign matter remains."
[0004] Patent Document 2 discloses "a cleaning blade for removing residual toner on an image carrier or a transfer body, the cleaning blade having a contact portion at the tip of a base portion, the base portion having a Shore D hardness of 50 or more and 80 or less, an ASTM D 1894 dynamic friction coefficient of 0.4 or less, and the contact portion having a Shore A hardness of 1 or more and 70 or less, and a Hayden type vs. polycarbonate dynamic friction coefficient of 1.2 or less at a friction speed of 2000 mm / min." [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2005-345493 A [Patent Document 2] JP 2010-102327 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present disclosure is to provide an image forming apparatus and an image forming method in which the occurrence of toner filming on the surface of an image carrier is suppressed and wear in the cleaning blade is suppressed, compared to an image forming apparatus and an image forming method equipped with a cleaning blade in which the total amount of F and Si present within 200 nm from the surface in contact with the image carrier is less than 75% of the total amount of F and Si present within 5 μm from the surface. [Means for solving the problem]
[0007] Means for solving the above problems include the following aspects. <1> An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; a developing means for developing an electrostatic image formed on the surface of the image carrier by the electrostatic image developer into a toner image, the developing means containing an electrostatic image developer containing a toner having toner particles, the release agent present in an area within 800 nm from the surface of the toner particles being 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent being 65° C. or more and 80° C. or less; a transfer means for transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a cleaning device having a cleaning blade which comes into contact with and cleans the outer peripheral surface of the image carrier, the cleaning blade being made of polyurethane resin, and the total amount of F and Si present within 200 nm from the surface in contact with the image carrier is 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming apparatus comprising: <2> the amount of the release agent present within 800 nm from the surface of the toner particle is 75% or more of the release agent in the entire toner particle; <1> 2. The image forming apparatus according to claim 1 . <3> The melting temperature of the release agent is 70° C. or higher and 75° C. or lower. <1> or <2> 2. The image forming apparatus according to claim 1 . <4> the 100% modulus at 23° C. of the surface of the cleaning blade that contacts the image carrier is 11 MPa or more and 22 MPa or less; <1> ~ <3> 13. The image forming apparatus according to claim 12, <5> the 100% modulus at 23° C. of the surface of the cleaning blade that contacts the image carrier is 15 MPa or more and 18 MPa or less; <4> 2. The image forming apparatus according to claim 1 . <6> the cleaning blade has a surface that comes into contact with the image carrier, and the total amount of F and Si present within 200 nm of the surface accounts for 85% or more of the total amount of F and Si present within 5 μm of the surface; <1> ~ <5> 13. The image forming apparatus according to claim 12, <7> the cleaning blade has a surface that comes into contact with the image carrier having a total amount of F and Si of 15 atm % or more; <1> ~ <6> 13. The image forming apparatus according to claim 12, <8> the cleaning blade has a surface that comes into contact with the image carrier having a total amount of F and Si of 18 atm % or more and 25 atm % or less; <7> 2. The image forming apparatus according to claim 1 . <9> the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface that contacts the image carrier of 0.3 atm % or more; <1> ~ <8> 13. The image forming apparatus according to claim 12, <10> the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface that contacts the image carrier of 1.0 atm % or more and 2.0 atm % or less; <9> 2. The image forming apparatus according to claim 1 . <11> the cleaning blade contains a silicone-based polymer in a surface layer that contacts the image carrier; <1> ~ <10> 13. The image forming apparatus according to claim 12, <12> the product of the static pressing pressure NF between the cleaning blade and the image carrier and the pressing angle WA is 40 or more and 60 or less; <1> ~ <11> 13. The image forming apparatus according to claim 12, <13> a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing, as a toner image, the electrostatic image formed on the surface of the image carrier using an electrostatic image developer containing a toner having toner particles, wherein a release agent present within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a cleaning step of contacting an outer peripheral surface of the image carrier with a cleaning blade made of polyurethane resin, the total amount of F and Si present within 200 nm from the surface in contact with the image carrier being 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming method comprising: Effect of the Invention
[0008] <1> According to the invention, an image forming apparatus is provided in which the occurrence of toner filming on the surface of an image carrier is suppressed and wear in the cleaning blade is suppressed, compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present within 200 nm from the surface in contact with the image carrier is less than 75% of the total amount of F and Si present within 5 μm from the surface. <2> According to the present invention, an image forming apparatus is provided that has excellent low-temperature fixing ability of images compared to an image forming apparatus in which the release agent present in the region within 800 nm from the surface of the toner particle is less than 75% of the release agent in the entire toner particle. <3> According to the invention, an image forming apparatus is provided which is superior in low-temperature image fixing ability compared to an image forming apparatus in which the melting temperature of the release agent is higher than 75°C, and an image forming apparatus is provided in which the occurrence of toner filming on the image carrier surface is suppressed compared to an image forming apparatus in which the melting temperature of the release agent is lower than 70°C. <4> or <5> According to the invention, an image forming apparatus is provided in which streak-like image defects caused by localized curling of the blade are suppressed compared to an image forming apparatus in which the 100% modulus at 23°C of the surface of the cleaning blade that contacts the image carrier is less than 11 MPa, and an image forming apparatus is provided in which the occurrence of toner filming on the image carrier surface is suppressed compared to an image forming apparatus in which the 100% modulus at 23°C of the surface of the cleaning blade that contacts the image carrier is more than 22 MPa. <6> According to the invention, an image forming apparatus is provided in which the occurrence of toner filming on the surface of an image carrier is suppressed and wear in the cleaning blade is suppressed, compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present within 200 nm from the surface that comes into contact with the image carrier is less than 85% of the total amount of F and Si present within 5 μm from the surface. <7> or <8> According to the present invention, an image forming apparatus is provided in which the occurrence of toner filming on the surface of an image carrier is suppressed and wear in the cleaning blade is suppressed, compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present on the surface that contacts the image carrier is less than 15 atm %. <9> or <10> According to the present invention, there is provided an image forming apparatus in which the occurrence of toner filming on the surface of the image carrier and wear of the cleaning blade are suppressed over time, as compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present at a position 50 nm from the surface that contacts the image carrier is less than 0.3 atm %. <11> According to the present invention, an image forming apparatus is provided in which the occurrence of toner filming on the surface of the image carrier is suppressed and wear in the cleaning blade is suppressed, compared to an image forming apparatus equipped with a cleaning blade that does not contain a silicone-based polymer in the surface layer that comes into contact with the image carrier and that contains a fluorine-based compound. <12> According to the invention, an image forming apparatus is provided in which the occurrence of toner slip-through at the contact point between the image carrier and the cleaning blade is suppressed compared to an image forming apparatus in which the product of the static pressing pressure NF and the pressing angle WA between the cleaning blade and the image carrier is less than 40, and an image forming apparatus is provided in which the occurrence of toner filming on the surface of the image carrier is further suppressed compared to an image forming apparatus in which the product of the pressing pressure NF and the pressing angle WA exceeds 60. <13> According to the invention, there is provided an image forming method in which the occurrence of toner filming on the surface of an image carrier is suppressed and wear in the cleaning blade is suppressed, as compared to an image forming method having a cleaning step using a cleaning blade in which the total amount of F and Si present within 200 nm from the surface in contact with the image carrier is less than 75% of the total amount of F and Si present within 5 μm from the surface. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of a layer structure of an electrophotographic photoreceptor used in the present embodiment. [Diagram 2] 1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic configuration diagram illustrating another example of an image forming apparatus according to the present embodiment. [Figure 4] 5A and 5B are schematic diagrams for explaining the pressing pressure of a cleaning blade against an image carrier. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the present embodiment, which is an example of the present disclosure, will be described. These descriptions and examples are merely illustrative of the embodiment, and do not limit the scope of the embodiment.
[0011] In the numerical ranges described in the present embodiment, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range described in the present embodiment. In addition, in the numerical ranges described in the present embodiment, the upper or lower limit of the numerical range may be replaced with a value shown in the examples. In this embodiment, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved. When the embodiment is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. Furthermore, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this. In this embodiment, each component may contain multiple types of corresponding substances. When referring to the amount of each component in the composition in this embodiment, if multiple types of substances corresponding to each component are present in the composition, the amount refers to the total amount of the multiple types of substances present in the composition, unless otherwise specified.
[0012] [Image forming equipment] The image forming apparatus according to this embodiment includes an image holder, a charging means for charging the surface of the image holder, an electrostatic image forming means for forming an electrostatic image on the surface of the charged image holder, a developing means that contains an electrostatic image developer containing a toner having toner particles and develops the electrostatic image formed on the surface of the image holder by the electrostatic image developer as a toner image, a transfer means that transfers the toner image formed on the surface of the image holder to the surface of a recording medium, and a cleaning device having a cleaning blade that contacts and cleans the outer peripheral surface of the image holder. The toner particles have a releasing agent present in a region within 800 nm from the surface that accounts for 70% or more of the releasing agent in the entire toner particle, and the melting temperature of the releasing agent is 65° C. or more and 80° C. or less. The cleaning blade is made of polyurethane resin, and the total amount of F and Si present within 200 nm from the surface in contact with the image carrier accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface.
[0013] The image forming apparatus according to the present embodiment, with the above-described configuration, suppresses the occurrence of toner filming on the surface of the image carrier and also suppresses wear on the cleaning blade. The reasons for this are presumed to be as follows.
[0014] From the viewpoint of improving the low-temperature fixability of an image, the use of a toner having toner particles with a low melting temperature wax unevenly distributed on the surface, specifically, a toner in which the release agent present in an area within 800 nm from the surface of the toner particles is 70% or more of the release agent of the entire toner particle, and the melting temperature of the release agent is 65°C or more and 80°C or less, has been considered. However, when toner particles with a low melting temperature wax unevenly distributed on the surface are used, toner filming may easily occur on the surface of the image carrier when an image with a low image density is repeatedly formed in a high-temperature and high-humidity environment. This is considered to be because the toner particles with the low melting temperature wax unevenly distributed on the surface as described above become soft and easily crushed in a high-temperature and high-humidity environment. Furthermore, it is considered that the pressure applied by the cleaning blade to each toner particle increases as the toner particles present on the image carrier are reduced by repeatedly forming an image with a low image density. In response to this, a method of suppressing the occurrence of toner filming can be considered by adjusting the cleaning blade pressed against the image carrier. For example, a method of suppressing toner filming can be exemplified by adjusting the pressing pressure NF (gf / mm) and pressing angle WA (°) of the cleaning blade to improve scraping performance. However, when the scraping performance of the cleaning blade is improved, the cleaning blade becomes worn out rapidly, and the life of the cleaning blade is shortened. Therefore, in addition to suppressing toner filming, it is also required to suppress the wear of the cleaning blade.
[0015] In contrast, the image forming apparatus according to the present embodiment uses a cleaning blade in which the total amount of F and Si present within 200 nm from the surface in contact with the image carrier is 75% or more of the total amount of F and Si present within 5 μm from the surface. In other words, F and Si are unevenly distributed in the cleaning blade near the contact portion with the image carrier. The presence of at least one of F and Si in the contact portion reduces the friction of the cleaning blade, and stabilizes the behavior at the tip of the contact portion. As a result, even when toner particles having low melting temperature wax unevenly distributed on the surface layer as described above are used, the occurrence of toner filming on the surface of the image carrier when low image density images are repeatedly formed in a high temperature and high humidity environment is suppressed. Furthermore, the presence of at least one of F and Si in the contact portion reduces the friction of the cleaning blade, and the wear of the cleaning blade is also suppressed.
[0016] From the above, it is presumed that the image forming apparatus according to this embodiment suppresses the occurrence of toner filming on the surface of the image carrier, and also suppresses wear on the cleaning blade.
[0017] (toner) The toner contained in the electrostatic image developer used in the image forming apparatus according to this embodiment will be described. The toner contains toner particles, and the release agent present within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particle, and the melting temperature of the release agent is 65°C or more and 80°C or less.
[0018] The toner particles contain a release agent, and may further contain a binder resin. The toner particles may also contain other internal additives such as a colorant.
[0019] -Release agent- The melting temperature of the release agent is 65° C. to 80° C., preferably 68° C. to 77° C., and more preferably 70° C. to 75° C. When the melting temperature of the release agent is 80° C. or less, the low-temperature fixing property of the image can be improved. On the other hand, when the melting temperature of the release agent is 65° C. or more, the occurrence of toner filming on the transfer belt surface can be suppressed.
[0020] The melting temperature of the release agent is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining the melting temperature in JIS K-7121-1987 "Method for measuring transition temperature of plastics."
[0021] More than 70% of the total release agent is present within 800 nm from the surface of the toner particles (hereinafter, the proportion of the release agent present within 800 nm from the surface of the toner particles is also referred to as the "surface proportion of the release agent"). The surface layer ratio of the release agent is 70% or more, preferably 75% or more, and more preferably 80% or more. The upper limit of the surface layer ratio of the release agent is preferably 100%. By making the surface layer ratio of the release agent 70% or more, the low temperature fixability of the image can be improved.
[0022] Here, a method for measuring the surface layer proportion of the release agent will be described. Samples and images for measurement are prepared in the following manner. The toner is mixed and embedded in an epoxy resin, and the epoxy resin is solidified. The solidified product is cut by an ultramicrotome device (UltracutUCT manufactured by Leica) to prepare a thin specimen having a thickness of 80 nm to 130 nm. Then, an SEM image of the thin specimen is obtained by an ultra-high resolution field emission scanning electron microscope (FE-SEM, S-4800 manufactured by Hitachi High-Technologies Corporation). In the SEM image, a cross section of a toner particle whose maximum length is 85% or more of the volume average particle diameter of the toner particle is selected, the domain of the release agent is observed, the area of the release agent of the entire toner particle and the area of the release agent present in the region within 800 nm from the surface of the toner particle are obtained, and the ratio of the two areas (area of the release agent present in the region within 800 nm from the surface of the toner particle / area of the release agent of the entire toner particle) is calculated. Then, this calculation is performed for 100 toner particles, and the average value is taken as the surface layer ratio of the release agent. The reason for selecting a toner particle cross section whose maximum length is 85% or more of the volume average particle diameter of the toner particle is that a cross section that is less than 85% of the volume average particle diameter is expected to be a cross section of the end of a toner particle, and the cross section of the end of a toner particle does not well reflect the state of the domains in the toner particle.
[0023] As a method for controlling the surface layer ratio of the release agent to 70% or more, for example, there is a method in which the toner particles have a core-shell structure and the release agent is used when forming the shell.
[0024] Examples of the release agent include hydrocarbon waxes such as paraffin wax, natural waxes such as carnauba wax, rice wax, candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, ester waxes such as fatty acid esters and montan acid esters, etc. The release agent is not limited to these. As the release agent, for example, a hydrocarbon wax is preferably used. The hydrocarbon wax is a wax having a hydrocarbon skeleton, and examples thereof include Fischer-Tropsch wax, polyethylene wax (wax having a polyethylene skeleton), polypropylene wax (wax having a polypropylene skeleton), paraffin wax (wax having a paraffin skeleton), and microcrystalline wax. Among these, from the viewpoint of fixability, the hydrocarbon wax is preferably Fischer-Tropsch wax, polyethylene wax, or polypropylene wax. In addition, from the viewpoint of fixability, it is preferable that a plurality of kinds of hydrocarbon waxes are contained in the toner particles. The proportion of the hydrocarbon wax in the total release agent is 85% by mass or more, preferably 95% by mass or more, and more preferably 100% by mass.
[0025] The content of the release agent is, for example, preferably from 1% by mass to 20% by mass, more preferably from 3% by mass to 20% by mass, even more preferably from 3% by mass to 15% by mass, and even more preferably from 5% by mass to 15% by mass, based on the total amount of the toner particles.
[0026] -Binding resin- As the binder resin, for example, a polyester resin is preferably used. The ratio of the polyester resin to the total binder resin is, for example, 75% by mass or more, preferably 90% by mass or more, and more preferably 100% by mass.
[0027] The polyester resin may be, for example, a known amorphous polyester resin. The polyester resin may be used in combination with a crystalline polyester resin together with the amorphous polyester resin. However, the content of the crystalline polyester resin is preferably in the range of 2% by mass to 40% by mass (preferably 2% by mass to 20% by mass) based on the total binder resin.
[0028] The "crystalline" nature of a resin refers to the presence of a clear endothermic peak rather than a stepwise change in the amount of endothermic heat in differential scanning calorimetry (DSC); specifically, the half-width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min). On the other hand, the term "amorphous" for a resin refers to a half-width exceeding 10° C., a stepwise change in endothermic heat quantity, or no clear endothermic peak being observed.
[0029] Amorphous polyester resin The amorphous polyester resin may be, for example, a condensation polymer of a polyvalent carboxylic acid and a polyhydric alcohol. The amorphous polyester resin may be a commercially available product or a synthesized product.
[0030] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferable as polyvalent carboxylic acids. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.
[0031] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, examples of polyhydric alcohols include aromatic diols and alicyclic diols, and more preferably aromatic diols. As the polyhydric alcohol, a polyhydric alcohol having a crosslinked or branched structure of three or more may be used in combination with the diol. Examples of the polyhydric alcohol having a trihydric or higher valence include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.
[0032] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K 7121-1987 "Method for measuring transition temperature of plastics."
[0033] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.
[0034] The amorphous polyester resin can be obtained by a known manufacturing method, for example, by carrying out the reaction while removing water and alcohol generated during condensation by setting the polymerization temperature to 180° C. or higher and 230° C. or lower, and reducing the pressure in the reaction system as necessary. If the raw material monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the solubilizing agent. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.
[0035] Crystalline polyester resin The crystalline polyester resin may be, for example, a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol. The crystalline polyester resin may be a commercially available product or a synthesized product. Here, the crystalline polyester resin is preferably a polycondensate using a polymerizable monomer having a linear aliphatic group rather than a polymerizable monomer having an aromatic group, since the crystalline polyester resin can easily form a crystalline structure.
[0036] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower alkyl esters (e.g., carbon number 1 to 5). As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.
[0037] Examples of polyhydric alcohols include aliphatic diols (for example, straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols. The polyhydric alcohol may be a trihydric or higher alcohol having a crosslinked or branched structure in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.
[0038] Here, the polyhydric alcohol has an aliphatic diol content of 80 mol % or more, preferably 90 mol % or more.
[0039] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."
[0040] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.
[0041] The crystalline polyester resin can be obtained by a known manufacturing method, for example, in the same manner as the amorphous polyester.
[0042] Here, the binder resin may be used in combination with the polyester resin, and preferably includes a styrene (meth)acrylic resin.
[0043] -Styrene (meth)acrylic resin- Styrene (meth)acrylic resin is a copolymer obtained by copolymerizing at least a monomer having a styrene skeleton and a monomer having a (meth)acryloyl group. "(meth)acrylic acid" is an expression that includes both "acrylic acid" and "methacrylic acid". Also, "(meth)acryloyl group" is an expression that includes both "acryloyl group" and "methacryloyl group".
[0044] Examples of monomers having a styrene skeleton (hereinafter referred to as "styrene-based monomers") include styrene, alkyl-substituted styrenes (e.g., α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, etc.), halogen-substituted styrenes (e.g., 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, etc.), vinylnaphthalene, etc. The styrene-based monomers may be used alone or in combination of two or more. Of these, as the styrene-based monomer, styrene is preferred from the viewpoints of ease of reaction, ease of reaction control, and availability.
[0045] Examples of monomers having a (meth)acryloyl group (hereinafter referred to as "(meth)acrylic monomers") include (meth)acrylic acid and (meth)acrylic acid esters. Examples of the (meth)acrylic acid ester include (meth)acrylic acid alkyl esters (e.g., n-methyl (meth)acrylate, n-ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isopentyl (meth)acrylate, amyl (meth)acrylate, Examples of the (meth)acrylate include neopentyl acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, etc.), aryl (meth)acrylate esters (for example, phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, t-butylphenyl (meth)acrylate, terphenyl (meth)acrylate, etc.), dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, β-carboxyethyl (meth)acrylate, and (meth)acrylamide. The (meth)acrylic acid monomers may be used alone or in combination of two or more.
[0046] The copolymerization ratio of the styrene monomer to the (meth)acrylic monomer (mass basis, styrene monomer / (meth)acrylic monomer) may be, for example, 85 / 15 to 70 / 30.
[0047] The styrene (meth)acrylic resin preferably has a crosslinked structure in terms of suppressing image offset. Examples of the styrene (meth)acrylic resin having a crosslinked structure include a crosslinked product obtained by copolymerizing at least a monomer having a styrene skeleton, a monomer having a (meth)acrylic acid skeleton, and a crosslinkable monomer.
[0048] The crosslinkable monomer may, for example, be a bifunctional or higher functional crosslinking agent. Examples of bifunctional crosslinking agents include divinylbenzene, divinylnaphthalene, di(meth)acrylate compounds (e.g., diethylene glycol di(meth)acrylate, methylene bis(meth)acrylamide, decanediol diacrylate, glycidyl (meth)acrylate, etc.), polyester type di(meth)acrylate, 2-([1'-methylpropylideneamino]carboxyamino)ethyl methacrylate, etc. Examples of polyfunctional crosslinking agents include tri(meth)acrylate compounds (e.g., pentaerythritol tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc.), tetra(meth)acrylate compounds (e.g., tetramethylolmethane tetra(meth)acrylate, oligoester (meth)acrylate, etc.), 2,2-bis(4-methacryloxy, polyethoxyphenyl)propane, diallyl phthalate, triallyl cyanurate, triallyl asocyanurate, triallyl isocyanurate, triallyl trimellitate, diaryl chlorendate, etc.
[0049] The copolymerization ratio of the crosslinkable monomer to the total monomers (mass basis, crosslinkable monomer / total monomers) may be, for example, 2 / 1000 to 30 / 1000.
[0050] The weight average molecular weight of the styrene (meth)acrylic resin is, for example, from 30,000 to 200,000, preferably from 40,000 to 100,000, and more preferably from 50,000 to 80,000, in terms of suppressing image offset. The weight average molecular weight of the styrene (meth)acrylic resin is a value measured by the same method as that for the weight average molecular weight of the polyester resin.
[0051] The content of the styrene (meth)acrylic resin is, for example, from 10% by mass to 30% by mass, preferably from 12% by mass to 28% by mass, and more preferably from 15% by mass to 25% by mass, in terms of achieving both the fluidity and storage stability of the toner and the suppression of image offset, relative to the toner particles.
[0052] Furthermore, other binder resins may be used in combination as the binder resin. Other binder resins include, for example, vinyl resins made of homopolymers of monomers such as styrenes (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), (meth)acrylic acid esters (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers made of a combination of two or more of these monomers. Examples of other binder resins include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the presence of these. These other binder resins may be used alone or in combination of two or more kinds.
[0053] The content of the binder resin is, for example, preferably from 40% by mass to 95% by mass, more preferably from 50% by mass to 90% by mass, and even more preferably from 60% by mass to 85% by mass, based on the total amount of the toner particles.
[0054] -Coloring agent- Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, ultramarine blue, and tetrahydrofuran. Examples of the dyes include various pigments such as phosphorus blue, chalcoil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate, and various dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, aniline black-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based dyes. The colorant may be used alone or in combination of two or more kinds.
[0055] The colorant may be surface-treated as necessary, or may be used in combination with a dispersant. In addition, a plurality of types of colorants may be used in combination.
[0056] The content of the colorant is, for example, preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner particles.
[0057] -Other additives- Examples of other additives in the toner include well-known additives such as magnetic materials, charge control agents, inorganic powders, etc. These additives are contained in the toner particles as internal additives.
[0058] -Characteristics of toner particles- The toner particles may be toner particles of a single layer structure, or may be toner particles of a so-called core-shell structure composed of a core (core particle) and a coating layer (shell layer) that coats the core, and the core-shell structure is preferable. The toner particles of the core-shell structure are preferably composed of, for example, a core composed of a binder resin and a colorant, and a coating layer composed of a binder resin and a release agent.
[0059] The volume average particle size (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm.
[0060] Various average particle sizes and various particle size distribution indexes of the toner particles are measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture diameter of 100 μm. The number of particles sampled is 50,000. Based on the measured particle size distribution, cumulative distributions of volume and number are drawn for each divided particle size range (channel) from the smallest diameter side, and the particle size at 16% of the cumulative size is defined as the volume particle size D16v, the number particle size D16p, the particle size at 50% of the cumulative size as the volume average particle size D50v, the number average particle size D50p, and the particle size at 84% of the cumulative size as the volume particle size D84v and the number particle size D84p. Using these, the volume average particle size distribution index (GSDv) is (D84v / D16v) 1 / 2 The number average particle size distribution index (GSDp) is (D84p / D16p) 1 / 2 It is calculated as:
[0061] The shape factor SF1 of the toner particles is preferably 110 or more and 150 or less, and more preferably 120 or more and 140 or less.
[0062] The shape factor SF1 is calculated by the following formula. Formula: SF1=(ML 2 / A)×(π / 4)×100 In the above formula, ML represents the absolute maximum length of the toner, and A represents the projected area of the toner. Specifically, the shape factor SF1 is quantified mainly by analyzing a microscope image or a scanning electron microscope image using an image analyzer, and is calculated as follows: That is, an optical microscope image of particles scattered on the surface of a slide glass is captured by a video camera into a Luzex image analyzer, the maximum length and projected area of 100 particles are determined, and the above formula is used to calculate the average value.
[0063] -External additives- The toner may further contain an external additive in addition to the toner particles. Examples of the external additive include inorganic particles, such as SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2)n, Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, and MgSO4.
[0064] The surface of the inorganic particles as an external additive may be subjected to a hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobic treatment agent is, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the inorganic particles.
[0065] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate (PMMA), and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles).
[0066] The amount of the external additive added is, for example, preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2.0% by mass, based on the toner particles.
[0067] -Toner manufacturing method- The toner used in the image forming apparatus according to the present embodiment is produced by producing toner particles, and then, when an external additive is contained, externally adding the external additive to the toner particles.
[0068] The toner particles may be produced by any of a dry production method (e.g., a kneading and pulverizing method, etc.) and a wet production method (e.g., an aggregation and coalescence method, a suspension polymerization method, a dissolution suspension method, etc.). There is no particular limitation on these production methods, and well-known production methods are used. Among them, it is preferable to obtain the toner particles by the aggregation and coalescence method.
[0069] Each step of the aggregation and coalescence method will be described in detail below. In the following description, a method for obtaining toner particles containing a colorant will be described, but the colorant is used as necessary. Of course, additives other than the colorant may be used.
[0070] ·Resin particle dispersion preparation process First, a resin particle dispersion liquid in which polyester resin particles serving as a binder resin are dispersed, a colorant dispersion liquid in which colorant particles are dispersed, and a release agent particle dispersion liquid in which release agent particles are dispersed are prepared.
[0071] The polyester resin particle dispersion liquid is prepared, for example, by dispersing polyester resin particles in a dispersion medium with the aid of a surfactant.
[0072] The dispersion medium used in the polyester resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water; alcohols; etc. These may be used alone or in combination of two or more.
[0073] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.
[0074] Examples of methods for dispersing polyester resin particles in a dispersion medium include general dispersion methods using a rotary shear homogenizer, a ball mill with media, a sand mill, a dyno mill, etc. Alternatively, polyester resin particles may be dispersed in a dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) to neutralize it, and then water (W phase) is added to invert the phase from W / O to O / W, dispersing the resin in particulate form in an aqueous medium.
[0075] The volume average particle size of the polyester resin particles dispersed in the polyester resin particle dispersion is, for example, preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm. The volume average particle diameter of the polyester resin particles is determined by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by Horiba, Ltd.), drawing a cumulative distribution for the volume of the divided particle size range (channel) from the small particle size side, and determining the particle size that accounts for 50% by volume of all particles as the volume average particle diameter D50v. The volume average particle diameters of particles in other dispersions are also measured in the same manner.
[0076] The content of the polyester resin particles contained in the polyester resin particle dispersion is preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.
[0077] The colorant dispersion and the release agent particle dispersion are also prepared in the same manner as the polyester resin particle dispersion. That is, the dispersion medium, the dispersion method, the volume average particle size of the particles, and the content of the particles in the polyester resin particle dispersion are the same for the colorant dispersion and the release agent particle dispersion.
[0078] ·First agglomerated particle formation step Next, the polyester resin particle dispersion and the colorant dispersion are mixed. Then, in the mixed dispersion, the polyester resin particles and the colorant particles are hetero-aggregated to form first aggregate particles containing the polyester resin particles and the colorant particles and having a diameter close to that of the target toner particles. If necessary, a release agent particle dispersion may also be mixed to cause the first aggregate particles to contain release agent particles.
[0079] Specifically, for example, an aggregating agent is added to the mixed dispersion, the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixed dispersion is heated to a temperature close to the glass transition temperature of the polyester resin (specifically, for example, −30° C. or more and −10° C. or less of the glass transition temperature of the polyester resin), and the particles dispersed in the mixed dispersion are aggregated to form first aggregated particles. In the first aggregate particle formation step, for example, the mixed dispersion may be stirred with a rotary shear homogenizer, an aggregating agent may be added at room temperature (e.g., 25°C), the pH of the mixed dispersion may be adjusted to an acidic state (e.g., pH 2 or more and 5 or less), a dispersion stabilizer may be added as necessary, and then the mixture may be heated.
[0080] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant contained in the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. When a metal complex is used as the flocculant, the amount of the flocculant used is reduced, and the charging characteristics are improved. An additive that forms a complex or a similar bond with the metal ions of the flocculant may be used together with the flocculant, and a chelating agent is preferably used as this additive.
[0081] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, for example, oxycarboxylic acid such as tartaric acid, citric acid, gluconic acid, etc., aminocarboxylic acid such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles.
[0082] ·Second agglomerated particle formation process After obtaining the first aggregated particle dispersion in which the first aggregated particles are dispersed, the first aggregated particle dispersion, the polyester resin particle dispersion, and the release agent particle dispersion are further mixed. The polyester resin particle dispersion and the release agent particle dispersion may be mixed in advance, and the mixture may be mixed into the first aggregated particle dispersion.
[0083] Then, in the mixed dispersion liquid in which the first aggregated particles, polyester resin particles, and release agent particles are dispersed, the polyester resin particles and release agent particles are aggregated so as to adhere to the surfaces of the first aggregated particles, thereby forming second aggregated particles.
[0084] Specifically, for example, in the first aggregate particle forming step, when the first aggregate particles reach a target particle size, a dispersion in which polyester resin particles and release agent particles are dispersed is mixed into the first aggregate particle dispersion, and then the mixed dispersion is heated at a temperature equal to or lower than the glass transition temperature of the polyester resin, and the pH of the mixed dispersion is adjusted to, for example, a range of about 6.5 to 8.5 to stop the progress of aggregation.
[0085] As a result, second aggregated particles are obtained, which are aggregated such that the polyester resin particles and the release agent particles adhere to the surfaces of the first aggregated particles.
[0086] ·Fusion / coalescence process Next, the second aggregate particle dispersion liquid in which the second aggregate particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the polyester resin (for example, a temperature 10° C. to 50° C. higher than the glass transition temperature of the polyester resin) to fuse and coalesce the second aggregate particles, thereby forming toner particles.
[0087] Through the above steps, toner particles are obtained. Note that the toner particles may be produced through a process in which, after obtaining the second aggregated particle dispersion in which the second aggregated particles are dispersed, the second aggregated particle dispersion is further mixed with a polyester resin particle dispersion in which polyester resin particles are dispersed, and the polyester resin particles are aggregated so that the polyester resin particles are further attached to the surfaces of the second aggregated particles, thereby forming third aggregated particles, and a process in which the third aggregated particle dispersion in which the third aggregated particles are dispersed is heated to fuse and coalesce the third aggregated particles, thereby forming toner particles.
[0088] After the fusion and coalescence process is completed, the toner particles formed in the solution are subjected to a known washing process, solid-liquid separation process, and drying process to obtain dry toner particles. In the washing step, from the viewpoint of electrostatic chargeability, it is preferable to carry out sufficient replacement washing with ion-exchanged water. In addition, the solid-liquid separation step is not particularly limited, but from the viewpoint of productivity, it is preferable to carry out suction filtration, pressure filtration, etc. In addition, in the drying step, there is no particular limit to the method, but from the viewpoint of productivity, it is preferable to carry out freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc.
[0089] The toner according to the present embodiment is produced, for example, by adding an external additive to dry toner particles and mixing them. The mixing may be performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sieve, an air sieve, etc.
[0090] -Electrostatic image developer- In this embodiment, the electrostatic image developer contained in the developing unit contains at least the above-mentioned toner. The electrostatic image developer may be a one-component developer containing only the toner, or may be a two-component developer in which the toner is mixed with a carrier.
[0091] The carrier is not particularly limited, and may be a known carrier. For example, the carrier may be a coated carrier in which the surface of a core material made of magnetic powder is coated with a resin; a magnetic powder dispersion type carrier in which magnetic powder is dispersed and mixed in a matrix resin; a resin impregnated type carrier in which porous magnetic powder is impregnated with a resin; etc. The magnetic powder dispersion type carrier and the resin impregnated type carrier may be a carrier in which the constituent particles of the carrier are used as a core material, and the surface of the carrier is coated with a resin.
[0092] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; magnetic oxides such as ferrite and magnetite; and the like.
[0093] Examples of the conductive particles include metals such as gold, silver, and copper; and particles of carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.
[0094] Examples of the coating resin and matrix resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylic acid ester copolymer, straight silicone resin containing organosiloxane bonds or modified products thereof, fluororesin, polyester, polycarbonate, phenolic resin, epoxy resin, etc. The coating resin and matrix resin may contain additives such as conductive materials.
[0095] To coat the surface of the core material with a resin, a method of coating with a coating layer forming solution in which the coating resin and various additives (used as necessary) are dissolved in an appropriate solvent can be mentioned. The solvent is not particularly limited, and may be selected taking into consideration the type of resin used, coating suitability, etc. Specific resin coating methods include an immersion method in which the core material is immersed in the coating layer forming solution; a spray method in which the coating layer forming solution is sprayed on the core material surface; a fluidized bed method in which the coating layer forming solution is sprayed on the core material while it is suspended in flowing air; and a kneader coater method in which the carrier core material and the coating layer forming solution are mixed in a kneader coater and then the solvent is removed; and the like.
[0096] The mixture ratio (mass ratio) of the toner and the carrier in the two-component developer is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.
[0097] (cleaning blade) The cleaning blade used in the image forming apparatus according to this embodiment will be described. The cleaning blade is made of polyurethane resin. The total amount of F and Si present within 200 nm from the surface (contact portion) of the cleaning blade that contacts the image carrier accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface.
[0098] The cleaning blade may be a single-layer blade consisting of one layer, a two-layer blade consisting of an edge layer (a layer that contacts the image carrier) and a back layer, or a laminate of three or more layers.
[0099] - Surface layer ratio of F and Si - The cleaning blade has a ratio (surface layer ratio of F and Si) of the total amount of F and Si present within 200 nm from the surface (contact portion) in contact with the image carrier to the total amount of F and Si present within 5 μm from the surface (surface layer ratio of F and Si) of 75% or more. When the surface layer ratio of F and Si at the contact portion of the cleaning blade is 75% or more, the contact portion of the cleaning blade has low friction, the occurrence of toner filming on the surface of the image carrier is suppressed, and the occurrence of wear in the cleaning blade is suppressed. The surface layer ratio of F and Si at the contact portion of the cleaning blade is more preferably 85% or more, and more preferably 90% or more. On the other hand, the upper limit of the surface layer ratio of F and Si at the contact portion of the cleaning blade is not particularly limited, but is preferably 95% or less, more preferably 93% or less. When the surface layer ratio of F and Si at the contact portion of the cleaning blade is 95% or less, the occurrence of belly contact (reduction in surface pressure) due to insufficient tack formation at the contact portion of the cleaning blade is suppressed.
[0100] - Surface F and Si content - The total amount of F and Si (surface F and Si amount) present on the surface (contact portion) of the cleaning blade that contacts the image carrier is preferably 15 atm% or more, more preferably 18 atm% or more, and even more preferably 20 atm% or more. By having the surface F and Si amount of the cleaning blade at the contact portion of the cleaning blade of 15 atm% or more, the contact portion of the cleaning blade has low friction, the occurrence of toner filming on the surface of the image carrier is suppressed, and the occurrence of wear in the cleaning blade is suppressed. The upper limit of the surface F and Si content at the contact portion of the cleaning blade is not particularly limited, but from the viewpoint of suppressing the occurrence of chipping at the contact portion of the cleaning blade, it is preferably 25 atm % or less, and more preferably 22 atm % or less.
[0101] -50nm position F and Si amount- The cleaning blade has a total amount of F and Si (amount of F and Si at 50 nm) of 0.3 atm% or more, more preferably 1.0 atm% or more, and even more preferably 1.5 atm% or more at a position 50 nm from the surface (contact portion) that contacts the image carrier. By having the amount of F and Si at 50 nm of the cleaning blade of 0.3 atm% or more, low friction at the contact portion of the cleaning blade is maintained, and the occurrence of toner filming on the surface of the image carrier and the occurrence of wear in the cleaning blade are suppressed over time. The upper limit values of F at 50 nm position and Si content of the cleaning blade are not particularly limited, but from the viewpoint of suppressing the occurrence of chipping at the contact portion of the cleaning blade over time, it is preferable that the upper limit value be 2.0 atm % or less, and more preferably 1.8 atm % or less.
[0102] A method for measuring the ratio of the total amount of F and Si present within 200 nm from the surface (contact portion) of a cleaning blade that contacts an image carrier to the total amount of F and Si present within 5 μm from the surface (surface layer ratio of F and Si) will be described. That is, a method for analyzing the amount of F element and the amount of Si element in the depth direction from the contact portion of the cleaning blade will be described. An area including the surface (contact portion) of the cleaning blade that comes into contact with the image carrier is cut out, and the amounts (atm%) of N, C, O, F, and Si elements are measured in the depth direction from the contact portion using XPS (Versa Probe II manufactured by Ulvac-PHI).
[0103] The total amount of F and Si present on the surface (contact portion) of the cleaning blade that comes into contact with the image carrier can be calculated by plotting the depth from the contact portion of the cleaning blade obtained by the above-mentioned analysis in the depth direction versus element ratio, with the area up to a depth of 5 μm being SA and the area up to a depth of 200 nm being SB, and calculating the ratio from the formula SB / SA × 100. The total amount of F and Si present at a position 50 nm from the surface (contact portion) of the cleaning blade that comes into contact with the image carrier can also be calculated in the same manner.
[0104] -100% Modulus (M100)- The 100% modulus at 23° C. of the surface (contact portion) of the cleaning blade that comes into contact with the image carrier is preferably 11 MPa or more and 22 MPa or less. Hereinafter, the 100% modulus at 23° C. of the contact portion of the cleaning blade is also referred to as “M100”. By setting M100 to 11 MPa or more, streak-like image defects caused by local blade curling are suppressed. From the viewpoint of suppressing streak-like image defects caused by local blade curling, M100 is more preferably 13 MPa or more, and even more preferably 15 MPa or more. Furthermore, by setting M100 to 22 MPa or less, toner filming on the image carrier is suppressed. From the viewpoint of suppressing toner filming, M100 is more preferably 20 MPa or less, and further preferably 18 MPa or less.
[0105] The above M100 is a value calculated from the stress at 100% strain using a dumbbell-shaped No. 3 test piece at a tensile speed of 500 mm / min in accordance with JIS K6251 (2010) at 23° C. The measurement device used is, for example, Strograph AE Elastomer manufactured by Toyo Seiki Co., Ltd. The method of making the M100 in the above range includes a method of adjusting the composition of the substrate of the cleaning blade. Specifically, when the substrate contains polyurethane rubber, the method of adjusting the content of the polyisocyanate component, when a crosslinking agent is used in the production of the substrate, the method of selecting at least one of the type and the amount of the crosslinking agent, and a combination of these methods. Note that, when the content of the polyisocyanate component is increased, the M100 becomes higher.
[0106] -composition- The cleaning blade is made of polyurethane resin.
[0107] Polyurethane resin The polyurethane resin is a polyurethane resin obtained by polymerizing at least a polyol component and a polyisocyanate component. If necessary, the polyurethane resin may be a polyurethane resin obtained by polymerizing a resin having a functional group capable of reacting with an isocyanate group of the polyisocyanate in addition to the polyol component.
[0108] The polyurethane resin preferably has a hard segment and a soft segment. The terms "hard segment" and "soft segment" refer to segments in which the material constituting the former is harder than the material constituting the latter, and the material constituting the latter is softer than the material constituting the former, in a polyurethane resin material. Examples of materials constituting the hard segment (hard segment materials) include low molecular weight polyol components among polyol components, resins having functional groups capable of reacting with isocyanate groups of polyisocyanates, etc. On the other hand, examples of materials constituting the soft segment (soft segment materials) include high molecular weight polyol components among polyol components.
[0109] Here, the average particle size of the hard segment aggregates is preferably 1 μm or more and 10 μm or less, and more preferably 1 μm or more and 5 μm or less. By setting the average particle size of the hard segment aggregates to 1 μm or more, the friction resistance on the surface of the contacting member is easily reduced, which stabilizes the blade behavior and makes it easier to suppress local wear. On the other hand, by setting the average particle size of the hard segment aggregates to 10 μm or less, the occurrence of chipping is easily suppressed.
[0110] The average particle size of the hard segment aggregates is measured as follows: Images were taken at a magnification of ×20 using a Pass BX51-P, and the images were binarized through image processing. The particle diameters (circle equivalent diameters) of the aggregates were measured at five points per cleaning blade (the particle diameters of five aggregates were measured at each point) for 20 cleaning blades, and the average particle diameter was calculated from a total of 500 particles. The images were binarized using the image processing software OLYMPUS Stream essentials (Olympus Corporation), and the hue / saturation / brightness thresholds were adjusted so that the crystalline parts and hard segment aggregates were black and the amorphous parts (corresponding to the soft segments) were white.
[0111] Polyol component The polyol component includes a high molecular weight polyol and a low molecular weight polyol.
[0112] The polymer polyol component is a polyol having a number average molecular weight of 500 or more (preferably 500 or more and 5000 or less). Examples of the polymer polyol component include well-known polyols such as polyester polyols obtained by dehydration condensation of low molecular weight polyols and dibasic acids, polycarbonate polyols obtained by reaction of low molecular weight polyols and alkyl carbonates, polycaprolactone polyols, and polyether polyols. Commercially available polymer polyols include, for example, PLACCEL 205 and PLACCEL 240 manufactured by Daicel Corporation.
[0113] Here, the number average molecular weight is a value measured by gel permeation chromatography (GPC). The same applies hereinafter.
[0114] These polymer polyols may be used alone or in combination of two or more kinds.
[0115] The polymerization ratio of the high molecular weight polyol component is preferably 30 mol % or more and 50 mol % or less, and more preferably 40 mol % or more and 50 mol % or less, based on the total polymerization components of the polyurethane resin.
[0116] The low molecular weight polyol component is a polyol having a molecular weight (number average molecular weight) of less than 500. The low molecular weight polyol is a material that functions as a chain extender and a crosslinking agent.
[0117] Examples of the low molecular weight polyol component include 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,20-eicosanediol. Among these, 1,4-butanediol is preferably used as the low molecular weight polyol component.
[0118] Examples of the low molecular weight polyol component include diols (2 functional), triols (3 functional), and tetraols (4 functional), which are well known as chain extenders and crosslinking agents. These polyols may be used alone or in combination of two or more kinds.
[0119] The polymerization ratio of the low molecular weight polyol component is preferably more than 50 mol% and 75 mol% or less, more preferably 52 mol% or more and 75 mol%, more preferably 55 mol% or more and 75 mol% or less, and even more preferably 55 mol% or more and 60 mol% or less, based on the total polymerization components of the polyurethane resin.
[0120] Polyisocyanate component Examples of the polyisocyanate component include 4,4'-diphenylmethane diisocyanate (MDI), 2,6-toluene diisocyanate (TDI), 1,6-hexanediisocyanate (TDI), isocyanate (HDI), 1,5-naphthalene diisocyanate (NDI), and 3,3-dimethylbiphenyl-4,4'-diisocyanate (TODI).
[0121] As the polyisocyanate component, 4,4'-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate (NDI), and hexamethylene diisocyanate (HDI) are more preferable.
[0122] These polyisocyanate components may be used alone or in combination of two or more kinds.
[0123] The polymerization ratio of the polyisocyanate component is preferably from 5 mol % to 25 mol %, and more preferably from 10 mol % to 20 mol %, based on the total polymerization components of the polyurethane resin.
[0124] Resins with functional groups that can react with isocyanate groups A resin having a functional group capable of reacting with an isocyanate group (hereinafter referred to as a "functional group-containing resin") is preferably a flexible resin, and from the viewpoint of flexibility, is more preferably an aliphatic resin having a linear structure. Specific examples of functional group-containing resins include acrylic resins containing two or more hydroxyl groups, polybutadiene resins containing two or more hydroxyl groups, and epoxy resins containing two or more epoxy groups.
[0125] An example of a commercially available acrylic resin containing two or more hydroxyl groups is Actflow (grades: UMB-2005B, UMB-2005P, UMB-2005, UME-2005, etc.) manufactured by Soken Chemical & Engineering Co., Ltd.
[0126] An example of a commercially available polybutadiene resin containing two or more hydroxyl groups is R-45HT manufactured by Idemitsu Kosan Co., Ltd.
[0127] The epoxy resin having two or more epoxy groups is not hard and brittle like conventional epoxy resins, but is more flexible and tough than conventional epoxy resins. For example, in terms of molecular structure, the epoxy resin preferably has a structure (flexible skeleton) in its main chain structure that can increase the mobility of the main chain, and examples of the flexible skeleton include an alkylene skeleton, a cycloalkane skeleton, and a polyoxyalkylene skeleton, and the polyoxyalkylene skeleton is particularly preferred. In terms of physical properties, epoxy resins with a lower viscosity relative to the molecular weight are preferred compared to conventional epoxy resins. Specifically, the weight average molecular weight is preferably within the range of 900±100, and the viscosity at 25°C is preferably within the range of 15000±5000 mPa·s, more preferably within the range of 15000±3000 mPa·s. Commercially available epoxy resins with these properties include, for example, EPLICON EXA-4850-150 manufactured by DIC.
[0128] The polymerization ratio of the functional group-containing resin is preferably set within a range that does not impair the properties of the cleaning blade.
[0129] -Method of manufacturing polyurethane resin The polyurethane resin is produced by a general polyurethane production method such as a prepolymer method or a one-shot method. The prepolymer method is suitable for this embodiment because it can produce polyurethane with excellent abrasion resistance and chipping resistance, but the production method is not limited. The cleaning blade is produced by forming the cleaning blade composition prepared by the above-mentioned method into a sheet shape by, for example, centrifugal molding or extrusion molding, and then cutting the sheet into a desired shape.
[0130] Examples of the catalyst used in the production of the polyurethane resin include amine compounds such as tertiary amines, quaternary ammonium salts, and organometallic compounds such as organotin compounds. Examples of the tertiary amine include trialkylamines such as triethylamine, tetraalkyldiamines such as N,N,N',N'-tetramethyl-1,3-butanediamine, aminoalcohols such as dimethylethanolamine, ethoxylated amines, ethoxylated diamines, ester amines such as bis(diethylethanolamine) adipate, triethylenediamine (TEDA), cyclohexylamine derivatives such as N,N-dimethylcyclohexylamine, morpholine derivatives such as N-methylmorpholine and N-(2-hydroxypropyl)-dimethylmorpholine, piperazine derivatives such as N,N'-diethyl-2-methylpiperazine and N,N'-bis-(2-hydroxypropyl)-2-methylpiperazine, and the like.
[0131] Examples of quaternary ammonium salts include 2-hydroxypropyltrimethylammonium octylate, 1,5-diazabicyclo[4.3.0]nonene-5 (DBN) octylate, 1,8-diazabicyclo[5.4.0]undecene-7 (DBU) octylate, DBU-oleate, DBU-p-toluenesulfonate, DBU-formate, and 2-hydroxypropyltrimethylammonium formate.
[0132] Examples of the organotin compound include dialkyltin compounds such as dibutyltin dilaurate and dibutyltin di(2-ethylhexoate), stannous 2-ethylcaproate, and stannous oleate.
[0133] Among these catalysts, the tertiary ammonium salt triethylenediamine (TEDA) is used in terms of hydrolysis resistance, and quaternary ammonium salts are preferred in terms of processability. Among the quaternary ammonium salts, 1,5-diazabicyclo[4.3.0]nonene-5 (DBN) octylate, 1,8-diazabicyclo[5.4.0]undecene-7 (DBU) octylate, and DBU formate are preferred, as they have high reactivity.
[0134] The content of the catalyst is preferably in the range of 0.0005% by mass to 0.03% by mass, and particularly preferably in the range of 0.001% by mass to 0.01% by mass, of the entire polyurethane resin constituting the contact member. These may be used alone or in combination of two or more.
[0135] - Fabrication of a two-layer cleaning blade For example, when the cleaning blade has a two-layer structure consisting of an edge layer and a back layer, the edge layer and the back layer are separately produced by the above-mentioned polyurethane resin production method, and the obtained edge layer and back layer are laminated together to produce the cleaning blade. In addition, when the hardness of the edge layer and the back surface layer is to be made different, the material of the polyurethane resin may be changed, for example, by changing the ratio of the hard segment and the soft segment.
[0136] -Contact area modification treatment In this embodiment, in order to set the ratio of the total amount of F and Si present within 200 nm from the surface (contact portion) of the cleaning blade that contacts the image carrier to the total amount of F and Si present within 5 μm from the surface (surface layer ratio of F and Si) within the above-mentioned range, it is preferable that the contact portion of the obtained cleaning blade has a modified layer that has been subjected to a surface modification treatment by penetrating at least one of F element and Si element.
[0137] The modified layer is a layer formed by impregnating the contact portion of the cleaning blade with a surface treatment liquid containing an isocyanate compound, a specific polymer having at least one of an F element and an Si element, and an organic solvent, and then hardening the surface treatment liquid (i.e., the isocyanate compound and the specific polymer). The modified layer is formed integrally with the surface layer of the contact portion so as to become gradually sparser from the surface toward the inside.
[0138] Examples of the isocyanate compound include 2,6-tolylene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), paraphenylene diisocyanate (PPDI), 1,5-naphthalene diisocyanate (NDI), 3,3'-dimethyldiphenyl-4,4'-diisocyanate (TODI), as well as polymers and modified products thereof. Examples of modified products of the isocyanate compound include urethane prepolymers in which an isocyanate compound is prepolymerized together with a polyol.
[0139] The specific polymer is preferably a compound that reacts with an isocyanate compound to form a chemical bond. Examples of acrylic polymers having siloxane bonds include block copolymers of (meth)acrylic acid esters and (meth)acrylic acid siloxane esters, and derivatives thereof. Note that "(meth)acrylic" means either acrylic or methacrylic, or both. Examples of acrylic polymers having fluorine atoms include block copolymers of (meth)acrylic acid esters and fluorinated alkyl (meth)acrylates, and derivatives thereof. The cleaning blade preferably contains a polymer having a siloxane bond (a silicone-based polymer) in the portion that comes into contact with the image carrier. From the viewpoint of solubility in organic solvents, the specific polymer is preferably a compound having a hydroxyl group, an alkyl group, or a carboxyl group.
[0140] The following methods can be used to confirm that the cleaning blade contains a specific polymer in the surface layer of the contact area, and that the surface layer contains a specific polymer that is an acrylic polymer. Specifically, the confirmation is performed by estimating the structure and analyzing the composition of the surface layer material of the contact area of the cleaning blade using an analytical method such as Fourier transform infrared spectrophotometer (FTIR) or X-ray photoelectron spectroscopy (XPS).
[0141] The content of the specific polymer in the surface treatment liquid is, for example, 8 parts by mass or more and 13 parts by mass or less, preferably 9 parts by mass or more and 13 parts by mass or less, and more preferably 10 parts by mass or more and 13 parts by mass or less, relative to 100 parts by mass of the isocyanate compound.
[0142] The organic solvent is preferably one that dissolves the specific polymer and is compatible with the isocyanate compound, and specific examples thereof include ethyl acetate, methyl ethyl ketone (MEK), toluene, acetone, cyclohexanone, etc. In addition, reactive diluents such as 2-hydroxyethyl acrylate, tetrahydrofurfuryl acrylate, 2-hydroxyethyl methacrylate, hydroxypropyl methacrylate, glycidyl methacrylate, neopentyl glycol diacrylate, hexanediol diacrylate, and trimethylolpropane triacrylate may also be used as the organic solvent.
[0143] The modified layer is formed, for example, by impregnating and applying the above-mentioned surface treatment liquid onto at least the contact portion of the cleaning blade, drying to remove the organic solvent, and then heating to form a hardened layer. The impregnation coating method is not particularly limited, and examples thereof include ordinary methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, curtain coating, etc. When the impregnation coating method is the dip coating method, the immersion time is, for example, in the range of 10 seconds or more and 60 seconds or less. Drying conditions after the impregnation coating include, for example, a temperature of 20° C. to 30° C. and a time of 1 minute to 10 minutes, and heat treatment conditions include, for example, a temperature of 50° C. to 80° C. and a time of 60 minutes to 90 minutes.
[0144] Pressing pressure NF, pressing angle WA The product (NF×WA) of the static pressing pressure NF between the cleaning blade and the image carrier and the pressing angle WA is preferably 40 or more and 60 or less. When NF×WA is 40 or more, the occurrence of toner slipping through at the contact point between the image carrier and the cleaning blade is suppressed. On the other hand, when NF×WA is 60 or less, the occurrence of toner filming on the surface of the image carrier is further suppressed. NF×WA is more preferably 45 or more and 58 or less, and even more preferably 50 or more and 56 or less.
[0145] Here, the pressing angle WA of the cleaning blade against the image carrier is:
[0146] The pressing pressure NF of the cleaning blade is calculated by the following formula. Formula: Pressing pressure NF = k × d In the formula, k is the spring constant specific to the cleaning blade, and d is the amount of penetration of the cleaning blade into the image carrier (see FIG. 4). The spring constant k specific to the cleaning blade is obtained by applying a displacement to the cleaning blade 12 and measuring the load with a load cell. The amount of penetration d of the cleaning blade into the image carrier is calculated by fixing the cleaning blade 12 to a supporting member and calculating the amount of displacement of the cleaning blade when it is brought into contact with the image carrier. In addition, the contact angle WA is calculated from the following formula using the free length L of the cleaning blade CB (the length of the portion not fixed by the support member CBC) and the set angle θ of the cleaning blade CB (i.e., the angle at the contact point between the straight portion of the cleaning blade CB (the portion not distorted by pressing against the image carrier BE) and the image carrier BE). Formula: Contact angle WA=θ-tan-1(3d / 2L) In FIG. 4, BE denotes an image carrier, CB denotes a cleaning blade, and CBS denotes a support member for supporting the cleaning blade.
[0147] The static pressing pressure NF (Normal Force) of the cleaning blade against the image carrier is preferably 1.5 gf / mm or more and 3.5 gf / mm or less, and more preferably 2.3 gf / mm or more and 3.2 gf / mm or less. The depth d of the cleaning blade penetrating into the image carrier is preferably 0 mm or more and 10 mm or less, and more preferably 0.01 mm or more and 5 mm or less.
[0148] (image holder) An image carrier used in the image forming apparatus according to the present embodiment will be described. In the present embodiment, an electrophotographic photoreceptor (hereinafter also referred to as "photoreceptor") is suitably used as the image carrier on whose surface a toner image is formed. The photoreceptor may, for example, have a configuration including a conductive substrate and a photosensitive layer provided on the conductive substrate.
[0149] Hereinafter, the electrophotographic photoreceptor will be described with reference to the drawings. 1 may be, for example, a photoreceptor 7 having a structure in which an undercoat layer 1, a charge generation layer 2, and a charge transport layer 3 are laminated in this order on a conductive support 4. The charge generation layer 2 and the charge transport layer 3 constitute a photosensitive layer 5.
[0150] The electrophotographic photoreceptor 7 may have a layer structure in which the undercoat layer 1 is not provided. The electrophotographic photoreceptor 7 may be a photoreceptor having a single-layer type photosensitive layer in which the functions of the charge generating layer 2 and the charge transport layer 3 are integrated. In the case of a photoreceptor having a single-layer type photosensitive layer, the single-layer type photosensitive layer constitutes the outermost layer. The electrophotographic photoreceptor 7 may be a photoreceptor having a surface protective layer on the charge transport layer 3 or on the single-layer photoreceptor. In the case of a photoreceptor having a surface protective layer, the surface protective layer constitutes the outermost surface layer.
[0151] Each layer of the electrophotographic photoreceptor will be described in detail below, with the reference numerals omitted.
[0152] (Conductive substrate) Examples of conductive substrates include metal plates, metal drums, and metal belts containing metals (aluminum, copper, zinc, chromium, nickel, molybdenum, vanadium, indium, gold, platinum, etc.) or alloys (stainless steel, etc.). Examples of conductive substrates include paper, resin films, belts, etc. coated, vapor-deposited, or laminated with conductive compounds (e.g., conductive polymers, indium oxide, etc.), metals (e.g., aluminum, palladium, gold, etc.) or alloys. Here, "conductive" refers to a material having a volume resistivity of 10 13 This means that the resistance is less than Ωcm.
[0153] When the electrophotographic photoreceptor is used in a laser printer, the surface of the conductive substrate is preferably roughened to a center line average roughness Ra of 0.04 μm to 0.5 μm in order to suppress interference fringes that occur when irradiating with laser light. When non-interfering light is used as the light source, roughening to prevent interference fringes is not particularly necessary, but it is suitable for extending the life of the conductive substrate since it suppresses the occurrence of defects due to unevenness on the surface.
[0154] Examples of methods for roughening the surface include wet honing, which involves spraying an abrasive suspended in water onto the conductive substrate; centerless grinding, in which the conductive substrate is pressed against a rotating grindstone and continuously ground; and anodizing.
[0155] As a method for roughening the surface, there can be mentioned a method in which, without roughening the surface of the conductive substrate, a conductive or semiconductive powder is dispersed in a resin to form a layer on the surface of the conductive substrate, and the surface is roughened by the particles dispersed in the layer.
[0156] In the roughening treatment by anodization, an oxide film is formed on the surface of a conductive substrate made of metal (e.g., aluminum) by anodizing the substrate in an electrolyte solution using the substrate as the anode. Examples of electrolyte solutions include sulfuric acid solution and oxalic acid solution. However, the porous anodic oxide film formed by anodization is chemically active in its original state, easily contaminated, and has a large resistance variation depending on the environment. Therefore, it is preferable to perform a sealing treatment on the porous anodic oxide film, in which the micropores of the oxide film are filled by volume expansion caused by hydration reaction in pressurized steam or boiling water (metal salts such as nickel may be added) to change the film into a more stable hydrated oxide.
[0157] The thickness of the anodic oxide film is preferably, for example, from 0.3 μm to 15 μm. If the thickness is within this range, the film tends to exhibit a barrier property against injection and tends to suppress an increase in residual potential due to repeated use.
[0158] The conductive substrate may be subjected to a treatment with an acidic treatment solution or a boehmite treatment. Treatment with an acid treatment liquid is carried out, for example, as follows. First, an acid treatment liquid containing phosphoric acid, chromic acid, and hydrofluoric acid is prepared. The compounding ratios of phosphoric acid, chromic acid, and hydrofluoric acid in the acid treatment liquid are, for example, in the range of 10% by mass to 11% by mass for phosphoric acid, 3% by mass to 5% by mass for chromic acid, and 0.5% by mass to 2% by mass for hydrofluoric acid, and the total concentration of these acids is preferably in the range of 13.5% by mass to 18% by mass. The treatment temperature is preferably, for example, 42° C. to 48° C. The film thickness of the coating is preferably 0.3 μm to 15 μm.
[0159] The boehmite treatment is carried out, for example, by immersing the material in pure water at 90°C to 100°C for 5 to 60 minutes, or by contacting the material with heated steam at 90°C to 120°C for 5 to 60 minutes. The thickness of the coating is preferably 0.1 μm to 5 μm. This may be further anodized using an electrolyte solution having low coating solubility, such as adipic acid, boric acid, borates, phosphates, phthalates, maleates, benzoates, tartrates, or citrates.
[0160] (subbing layer) The undercoat layer is, for example, a layer containing inorganic particles and a binder resin.
[0161] As inorganic particles, for example, powder resistivity (volume resistivity) of 10 2 Ωcm or more 10 11 Examples of such particles include inorganic particles with a particle size of Ωcm or less. Among these, examples of inorganic particles having the above-mentioned resistance value include metal oxide particles such as tin oxide particles, titanium oxide particles, zinc oxide particles, and zirconium oxide particles, and zinc oxide particles are particularly preferred.
[0162] The specific surface area of inorganic particles by the BET method is, for example, 10 m 2 / g or higher is preferable. The volume average particle size of the inorganic particles is, for example, from 50 nm to 2000 nm (preferably from 60 nm to 1000 nm).
[0163] The content of the inorganic particles is, for example, preferably from 10% by mass to 80% by mass, more preferably from 40% by mass to 80% by mass, based on the binder resin.
[0164] The inorganic particles may be surface-treated. Two or more types of inorganic particles having different surface treatments or different particle sizes may be used in combination.
[0165] Examples of the surface treatment agent include a silane coupling agent, a titanate coupling agent, an aluminum coupling agent, a surfactant, etc. In particular, a silane coupling agent is preferred, and a silane coupling agent having an amino group is more preferred.
[0166] Examples of silane coupling agents having an amino group include, but are not limited to, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, and N,N-bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane.
[0167] Silane coupling agents may be used in combination of two or more kinds. For example, a silane coupling agent having an amino group may be used in combination with another silane coupling agent. Examples of other silane coupling agents include, but are not limited to, vinyltrimethoxysilane, 3-methacryloxypropyl-tris(2-methoxyethoxy)silane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, vinyltriacetoxysilane, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N,N-bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, and 3-chloropropyltrimethoxysilane.
[0168] The surface treatment method using the surface treatment agent may be any known method, and may be either a dry method or a wet method.
[0169] The amount of the surface treatment agent to be used is preferably, for example, 0.5% by mass or more and 10% by mass or less based on the inorganic particles.
[0170] Here, it is preferable that the undercoat layer contains an electron accepting compound (acceptor compound) together with the inorganic particles, from the viewpoints of improving the long-term stability of electrical properties and carrier blocking properties.
[0171] Examples of the electron-accepting compound include electron-transporting substances such as quinone compounds such as chloranil and bromoanil; tetracyanoquinodimethane compounds; fluorenone compounds such as 2,4,7-trinitrofluorenone and 2,4,5,7-tetranitro-9-fluorenone; oxadiazole compounds such as 2-(4-biphenyl)-5-(4-t-butylphenyl)-1,3,4-oxadiazole, 2,5-bis(4-naphthyl)-1,3,4-oxadiazole and 2,5-bis(4-diethylaminophenyl)-1,3,4-oxadiazole; xanthone compounds; thiophene compounds; and diphenoquinone compounds such as 3,3',5,5'-tetra-t-butyldiphenoquinone. In particular, the electron-accepting compound is preferably a compound having an anthraquinone structure. Examples of the compound having an anthraquinone structure include hydroxyanthraquinone compounds, aminoanthraquinone compounds, and aminohydroxyanthraquinone compounds, and more specifically, anthraquinone, alizarin, quinizarin, anthrarufin, and purpurin.
[0172] The electron accepting compound may be contained in the undercoat layer in a dispersed state together with the inorganic particles, or may be contained in a state of being attached to the surfaces of the inorganic particles.
[0173] The method for attaching the electron accepting compound to the surface of the inorganic particles may be, for example, a dry method or a wet method.
[0174] The dry method is, for example, a method in which an electron-accepting compound is attached to the surface of inorganic particles by dropping an electron-accepting compound directly or dissolved in an organic solvent or spraying it together with dry air or nitrogen gas while stirring inorganic particles with a mixer or the like that exerts a large shearing force. The dropping or spraying of the electron-accepting compound is preferably performed at a temperature below the boiling point of the solvent. After dropping or spraying the electron-accepting compound, baking may be performed at 100° C. or higher. The temperature and time of baking are not particularly limited as long as electrophotographic properties can be obtained.
[0175] The wet method is a method in which, for example, an electron-accepting compound is added while dispersing inorganic particles in a solvent by stirring, ultrasonic waves, a sand mill, an attritor, a ball mill, etc., and the inorganic particles are stirred or dispersed, and then the solvent is removed to attach the electron-accepting compound to the surface of the inorganic particles. The solvent is removed, for example, by filtration or distillation. After the solvent is removed, baking may be performed at 100°C or higher. The baking temperature and time are not particularly limited as long as electrophotographic properties are obtained. In the wet method, moisture contained in the inorganic particles may be removed before adding the electron-accepting compound, and examples of such methods include a method of removing the moisture while stirring and heating in a solvent, and a method of removing the moisture by azeotropy with the solvent.
[0176] The attachment of the electron accepting compound may be carried out before or after the inorganic particles are subjected to a surface treatment with a surface treatment agent, or the attachment of the electron accepting compound and the surface treatment with the surface treatment agent may be carried out simultaneously.
[0177] The content of the electron accepting compound is, for example, from 0.01% by mass to 20% by mass, and preferably from 0.01% by mass to 10% by mass, based on the inorganic particles.
[0178] Examples of the binder resin used in the undercoat layer include known materials such as acetal resins (e.g., polyvinyl butyral, etc.), polyvinyl alcohol resins, polyvinyl acetal resins, casein resins, polyamide resins, cellulose resins, gelatin, polyurethane resins, polyester resins, unsaturated polyester resins, methacrylic resins, acrylic resins, polyvinyl chloride resins, polyvinyl acetate resins, vinyl chloride-vinyl acetate-maleic anhydride resins, silicone resins, silicone-alkyd resins, urea resins, phenol resins, phenol-formaldehyde resins, melamine resins, urethane resins, alkyd resins, and epoxy resins; zirconium chelate compounds; titanium chelate compounds; aluminum chelate compounds; titanium alkoxide compounds; organic titanium compounds; and silane coupling agents. Examples of the binder resin used in the undercoat layer include charge transporting resins having charge transporting groups, conductive resins (such as polyaniline, etc.), and the like.
[0179] Among these, the binder resin used in the undercoat layer is preferably a resin that is insoluble in the coating solvent of the upper layer, and in particular, a resin obtained by reacting at least one resin selected from the group consisting of thermosetting resins such as urea resins, phenol resins, phenol-formaldehyde resins, melamine resins, urethane resins, unsaturated polyester resins, alkyd resins, and epoxy resins, with a curing agent is preferred. When two or more of these binder resins are used in combination, the mixing ratio is set as necessary.
[0180] The undercoat layer may contain various additives for improving electrical properties, environmental stability, and image quality. Examples of the additives include known materials such as polycyclic condensation and azo-based electron transport pigments, zirconium chelate compounds, titanium chelate compounds, aluminum chelate compounds, titanium alkoxide compounds, organic titanium compounds, silane coupling agents, etc. As described above, silane coupling agents are used for surface treatment of inorganic particles, and may also be added to the undercoat layer as an additive.
[0181] Examples of silane coupling agents as additives include vinyltrimethoxysilane, 3-methacryloxypropyl-tris(2-methoxyethoxy)silane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, vinyltriacetoxysilane, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N,N-bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, 3-chloropropyltrimethoxysilane, and the like.
[0182] Examples of the zirconium chelate compound include zirconium butoxide, zirconium ethyl acetoacetate, zirconium triethanolamine, acetylacetonate zirconium butoxide, ethyl acetoacetate zirconium butoxide, zirconium acetate, zirconium oxalate, zirconium lactate, zirconium phosphonate, zirconium octanoate, zirconium naphthenate, zirconium laurate, zirconium stearate, zirconium isostearate, methacrylate zirconium butoxide, stearate zirconium butoxide, and isostearate zirconium butoxide.
[0183] Examples of titanium chelate compounds include tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, tetra(2-ethylhexyl) titanate, titanium acetylacetonate, polytitanium acetylacetonate, titanium octylene glycolate, titanium lactate ammonium salt, titanium lactate, titanium lactate ethyl ester, titanium triethanolamine, and polyhydroxytitanium stearate.
[0184] Examples of aluminum chelate compounds include aluminum isopropylate, monobutoxyaluminum diisopropylate, aluminum butyrate, diethylacetoacetate aluminum diisopropylate, and aluminum tris(ethylacetoacetate).
[0185] These additives may be used alone or as a mixture or polycondensation product of a plurality of compounds.
[0186] The undercoat layer preferably has a Vickers hardness of 35 or more. The surface roughness (ten-point average roughness) of the undercoat layer is preferably adjusted to between 1 / (4n) (n is the refractive index of the upper layer) and 1 / 2 of the wavelength λ of the exposure laser used in order to suppress moire images. Resin particles or the like may be added to the undercoat layer to adjust the surface roughness. Examples of the resin particles include silicone resin particles and crosslinked polymethyl methacrylate resin particles. The surface of the undercoat layer may be polished to adjust the surface roughness. Examples of the polishing method include buffing, sandblasting, wet honing, grinding, and the like.
[0187] The formation of the undercoat layer is not particularly limited, and a well-known formation method can be used. For example, the undercoat layer can be formed by forming a coating film of a coating solution for forming the undercoat layer in which the above-mentioned components are added to a solvent, drying the coating film, and heating it as necessary.
[0188] Examples of the solvent for preparing the coating liquid for forming the undercoat layer include known organic solvents, such as alcohol-based solvents, aromatic hydrocarbon solvents, halogenated hydrocarbon solvents, ketone-based solvents, ketone alcohol-based solvents, ether-based solvents, and ester-based solvents. Specific examples of these solvents include ordinary organic solvents such as methanol, ethanol, n-propanol, iso-propanol, n-butanol, benzyl alcohol, methyl cellosolve, ethyl cellosolve, acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, ethyl acetate, n-butyl acetate, dioxane, tetrahydrofuran, methylene chloride, chloroform, chlorobenzene, and toluene.
[0189] Examples of the method for dispersing the inorganic particles when preparing the coating liquid for forming the undercoat layer include known methods such as those using a roll mill, a ball mill, a vibrating ball mill, an attritor, a sand mill, a colloid mill, and a paint shaker.
[0190] Examples of the method for applying the coating liquid for forming the undercoat layer onto the conductive substrate include ordinary methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, and curtain coating.
[0191] The thickness of the undercoat layer is set, for example, preferably at least 15 μm, and more preferably within the range of from 20 μm to 50 μm.
[0192] (Middle class) Although not shown, an intermediate layer may be further provided between the undercoat layer and the photosensitive layer. The intermediate layer is, for example, a layer containing a resin. Examples of the resin used in the intermediate layer include polymer compounds such as acetal resins (e.g., polyvinyl butyral, etc.), polyvinyl alcohol resins, polyvinyl acetal resins, casein resins, polyamide resins, cellulose resins, gelatin, polyurethane resins, polyester resins, methacrylic resins, acrylic resins, polyvinyl chloride resins, polyvinyl acetate resins, vinyl chloride-vinyl acetate-maleic anhydride resins, silicone resins, silicone-alkyd resins, phenol-formaldehyde resins, and melamine resins. The intermediate layer may be a layer containing an organometallic compound. Examples of the organometallic compound used in the intermediate layer include organometallic compounds containing metal atoms such as zirconium, titanium, aluminum, manganese, and silicon. The compounds used in the intermediate layer may be used alone or as a mixture or polycondensation product of a plurality of compounds.
[0193] Among these, the intermediate layer is preferably a layer containing an organometallic compound containing zirconium atoms or silicon atoms.
[0194] The formation of the intermediate layer is not particularly limited, and a well-known formation method can be used. For example, the intermediate layer can be formed by forming a coating film of a coating liquid for forming an intermediate layer in which the above components are added to a solvent, drying the coating film, and heating it if necessary. The intermediate layer can be formed by any of the usual coating methods, such as dip coating, push-up coating, wire bar coating, spray coating, blade coating, knife coating and curtain coating.
[0195] The thickness of the intermediate layer is preferably set in the range of, for example, 0.1 μm to 3 μm. The intermediate layer may also be used as an undercoat layer.
[0196] (Charge generation layer) The charge generation layer is, for example, a layer containing a charge generation material and a binder resin. The charge generation layer may also be a vapor deposition layer of the charge generation material. The vapor deposition layer of the charge generation material is suitable for use with a non-coherent light source such as an LED (Light Emitting Diode) or an organic EL (Electro-Luminescence) image array.
[0197] Examples of the charge generating material include azo pigments such as bisazo and trisazo; condensed aromatic pigments such as dibromoanthanthrone; perylene pigments; pyrrolopyrrole pigments; phthalocyanine pigments; zinc oxide; and trigonal selenium.
[0198] Among these, in order to accommodate laser exposure in the near infrared region, it is preferable to use a metal phthalocyanine pigment or a metal-free phthalocyanine pigment as the charge generating material, specifically, for example, hydroxygallium phthalocyanine, chlorogallium phthalocyanine, dichlorotin phthalocyanine, or titanyl phthalocyanine.
[0199] On the other hand, in order to accommodate laser exposure in the near ultraviolet region, preferred charge generating materials include condensed aromatic pigments such as dibromoanthanthrone, thioindigo pigments, porphyrazine compounds, zinc oxide, trigonal selenium, and bisazo pigments.
[0200] The above charge generating materials may be used when using incoherent light sources such as LEDs and organic EL image arrays that emit light at a central wavelength of 450 nm to 780 nm, but from the viewpoint of resolution, when using a thin photosensitive layer of 20 μm or less, the electric field strength in the photosensitive layer becomes high, and a decrease in charging due to charge injection from the substrate, so-called black spots, is likely to occur as an image defect. This becomes more noticeable when using charge generating materials that are p-type semiconductors such as trigonal selenium and phthalocyanine pigments and are prone to generating dark current.
[0201] In contrast, when an n-type semiconductor such as a fused aromatic pigment, a perylene pigment, or an azo pigment is used as the charge generating material, dark current is unlikely to occur, and image defects called black spots can be suppressed even when the material is made into a thin film. The n-type is determined by the polarity of the photocurrent that flows using the commonly used time-of-flight method, and those that easily pass electrons as carriers rather than holes are considered to be n-type.
[0202] The binder resin used in the charge generating layer may be selected from a wide range of insulating resins, and may also be selected from organic photoconductive polymers such as poly-N-vinylcarbazole, polyvinylanthracene, polyvinylpyrene, polysilane, and the like. Examples of the binder resin include polyvinyl butyral resin, polyarylate resin (polycondensation product of bisphenols and aromatic dicarboxylic acid, etc.), polycarbonate resin, polyester resin, phenoxy resin, vinyl chloride-vinyl acetate copolymer, polyamide resin, acrylic resin, polyacrylamide resin, polyvinylpyridine resin, cellulose resin, urethane resin, epoxy resin, casein, polyvinyl alcohol resin, polyvinylpyrrolidone resin, etc. Here, "insulating" means a material having a volume resistivity of 10 13 This means that the resistance is Ωcm or more. These binder resins may be used alone or in combination of two or more.
[0203] The compounding ratio of the charge generating material to the binder resin is preferably within a range of 10:1 to 1:10 by mass.
[0204] The charge generating layer may contain other well-known additives.
[0205] The formation of the charge generation layer is not particularly limited, and a known formation method is used, for example, by forming a coating film of a coating solution for forming a charge generation layer in which the above-mentioned components are added to a solvent, drying the coating film, and heating it as necessary. The formation of the charge generation layer may be performed by vapor deposition of a charge generation material. The formation of the charge generation layer by vapor deposition is particularly suitable when a condensed ring aromatic pigment or a perylene pigment is used as the charge generation material.
[0206] Examples of the solvent for preparing the coating liquid for forming the charge generating layer include methanol, ethanol, n-propanol, n-butanol, benzyl alcohol, methyl cellosolve, ethyl cellosolve, acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, n-butyl acetate, dioxane, tetrahydrofuran, methylene chloride, chloroform, chlorobenzene, toluene, etc. These solvents may be used alone or in combination of two or more.
[0207] Examples of methods for dispersing particles (e.g., charge generating material) in the coating liquid for forming a charge generating layer include media dispersers such as ball mills, vibration ball mills, attritors, sand mills, and horizontal sand mills, and medialess dispersers such as stirrers, ultrasonic dispersers, roll mills, and high-pressure homogenizers. Examples of high-pressure homogenizers include a collision method in which the dispersion liquid is dispersed by liquid-liquid collision or liquid-wall collision under high pressure, and a penetration method in which the dispersion liquid is dispersed by penetrating a fine flow path under high pressure. During this dispersion, it is effective to adjust the average particle size of the charge generating material in the coating liquid for forming the charge generating layer to 0.5 μm or less, preferably 0.3 μm or less, and more preferably 0.15 μm or less.
[0208] Examples of a method for applying the coating liquid for forming the charge generating layer onto the undercoat layer (or onto the intermediate layer) include conventional methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, and curtain coating.
[0209] The thickness of the charge generating layer is set, for example, preferably in the range of 0.1 μm or more and 5.0 μm or less, and more preferably in the range of 0.2 μm or more and 2.0 μm or less.
[0210] (charge transport layer) The charge transport layer is, for example, a layer containing a charge transport material and a binder resin, and may be a layer containing a polymer charge transport material.
[0211] Examples of the charge transport material include electron transporting compounds such as quinone compounds such as p-benzoquinone, chloranil, bromanil, and anthraquinone; tetracyanoquinodimethane compounds; fluorenone compounds such as 2,4,7-trinitrofluorenone; xanthone compounds; benzophenone compounds; cyanovinyl compounds; and ethylene compounds. Examples of the charge transport material include hole transporting compounds such as triarylamine compounds, benzidine compounds, arylalkane compounds, aryl-substituted ethylene compounds, stilbene compounds, anthracene compounds, and hydrazone compounds. These charge transport materials may be used alone or in combination, but are not limited to these.
[0212] As the charge transport material, from the viewpoint of charge mobility, a triarylamine derivative represented by the following structural formula (a-1) and a benzidine derivative represented by the following structural formula (a-2) are preferred.
[0213] [ka]
[0214] In structural formula (a-1), Ar T1 , Ar T2 , and Ar T3 each independently represents a substituted or unsubstituted aryl group, -CH-C(R T4 )=C(R T5 )(R T6 ), or -CH-CH=CH-CH=C(R T7 )(R T8 ) is shown. T4 , R T5 , R T6 , R T7 , and R T8 each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group, or a substituted or unsubstituted aryl group. Examples of the substituent for each of the above groups include a halogen atom, an alkyl group having from 1 to 5 carbon atoms, and an alkoxy group having from 1 to 5 carbon atoms. Examples of the substituent for each of the above groups also include a substituted amino group substituted with an alkyl group having from 1 to 3 carbon atoms.
[0215] [ka]
[0216] In structural formula (a-2), R T91 and R T92 R each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 5 carbon atoms, or an alkoxy group having 1 to 5 carbon atoms. T101 , R T102 , R T111 and R T112 each independently represents a halogen atom, an alkyl group having from 1 to 5 carbon atoms, an alkoxy group having from 1 to 5 carbon atoms, an amino group substituted with an alkyl group having from 1 to 2 carbon atoms, a substituted or unsubstituted aryl group, -C(R T12 )=C(R T13 )(R T14 ), or -CH=CH-CH=C(R T15 )(R T16 ) and R T12 , R T13 , R T14 , R T15 and R T16 each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group, or a substituted or unsubstituted aryl group. Tm1, Tm2, Tn1, and Tn2 each independently represent an integer of 0 or more and 2 or less. Examples of the substituent for each of the above groups include a halogen atom, an alkyl group having from 1 to 5 carbon atoms, and an alkoxy group having from 1 to 5 carbon atoms. Examples of the substituent for each of the above groups also include a substituted amino group substituted with an alkyl group having from 1 to 3 carbon atoms.
[0217] Among the triarylamine derivatives represented by the structural formula (a-1) and the benzidine derivatives represented by the structural formula (a-2), in particular, "-C6H4-CH=CH-CH=C(R T7)(R T8 )" and triarylamine derivatives having "-CH=CH-CH=C(R T15 )(R T16 ) is preferable from the viewpoint of charge mobility.
[0218] As the polymer charge transport material, known materials having charge transport properties such as poly-N-vinylcarbazole and polysilane are used. In particular, polyester polymer charge transport materials are particularly preferred. The polymer charge transport material may be used alone or in combination with a binder resin.
[0219] Examples of the binder resin used in the charge transport layer include polycarbonate resin, polyester resin, polyarylate resin, methacrylic resin, acrylic resin, polyvinyl chloride resin, polyvinylidene chloride resin, polystyrene resin, polyvinyl acetate resin, styrene-butadiene copolymer, vinylidene chloride-acrylonitrile copolymer, vinyl chloride-vinyl acetate copolymer, vinyl chloride-vinyl acetate-maleic anhydride copolymer, silicone resin, silicone alkyd resin, phenol-formaldehyde resin, styrene-alkyd resin, poly-N-vinylcarbazole, polysilane, etc. Among these, polycarbonate resin or polyarylate resin is suitable as the binder resin. These binder resins are used alone or in combination of two or more. The compounding ratio of the charge transport material to the binder resin is preferably from 10:1 to 1:5 by mass.
[0220] The charge transport layer may contain other well-known additives.
[0221] The formation of the charge transport layer is not particularly limited, and a known formation method can be used. For example, the charge transport layer can be formed by forming a coating film of a coating liquid for forming the charge transport layer in which the above components are added to a solvent, drying the coating film, and heating it as necessary.
[0222] Examples of solvents for preparing the coating liquid for forming the charge transport layer include ordinary organic solvents such as aromatic hydrocarbons such as benzene, toluene, xylene, and chlorobenzene, ketones such as acetone and 2-butanone, halogenated aliphatic hydrocarbons such as methylene chloride, chloroform, and ethylene chloride, and cyclic or linear ethers such as tetrahydrofuran and ethyl ether. These solvents may be used alone or in combination of two or more.
[0223] Examples of a coating method for coating the coating liquid for forming the charge transport layer on the charge generating layer include ordinary methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating and curtain coating.
[0224] The thickness of the charge transport layer is set, for example, preferably in the range of 5 μm or more and 50 μm or less, and more preferably in the range of 10 μm or more and 30 μm or less.
[0225] (protective layer) A protective layer is provided on the photosensitive layer as necessary for the purpose of, for example, preventing chemical changes in the photosensitive layer when the photosensitive layer is charged and further improving the mechanical strength of the photosensitive layer. Therefore, it is preferable to apply a layer composed of a cured film (crosslinked film) as the protective layer. Examples of such a layer include the following layers 1) and 2).
[0226] 1) A layer composed of a cured film of a composition containing a reactive group-containing charge transport material having a reactive group and a charge transport skeleton in the same molecule (i.e., a layer containing a polymer or crosslinked product of the reactive group-containing charge transport material). 2) A layer composed of a cured film of a composition containing a non-reactive charge transport material and a reactive group-containing non-charge transport material that does not have a charge transport skeleton and has a reactive group (i.e., a layer containing a non-reactive charge transport material and a polymer or crosslinked body of the reactive group-containing non-charge transport material).
[0227] The reactive group of the reactive group-containing charge transport material may be a chain polymerizable group, an epoxy group, -OH, -OR (wherein R represents an alkyl group), -NH2, -SH, -COOH, or -SiR. Q1 3-Qn (OR Q2 ) Qn [However, R Q1 represents a hydrogen atom, an alkyl group, or a substituted or unsubstituted aryl group; R Q2 represents a hydrogen atom, an alkyl group, or a trialkylsilyl group; Qn represents an integer of 1 to 3.
[0228] The chain polymerizable group is not particularly limited as long as it is a functional group capable of radical polymerization, and is, for example, a functional group having a group containing at least a carbon double bond.Specific examples include groups containing at least one selected from vinyl groups, vinyl ether groups, vinyl thioether groups, vinylphenyl groups, acryloyl groups, methacryloyl groups, and derivatives thereof.Among them, the chain polymerizable group is preferably a group containing at least one selected from vinyl groups, vinylphenyl groups, acryloyl groups, methacryloyl groups, and derivatives thereof, because of its excellent reactivity.
[0229] The charge transporting skeleton of the reactive group-containing charge transporting material is not particularly limited as long as it is a known structure in electrophotographic photoreceptors, and examples thereof include a skeleton derived from a nitrogen-containing hole transporting compound such as a triarylamine compound, a benzidine compound, a hydrazone compound, etc., and a structure conjugated with a nitrogen atom. Among these, a triarylamine skeleton is preferred.
[0230] The reactive group-containing charge transport material having a reactive group and a charge transporting skeleton, the non-reactive charge transport material, and the reactive group-containing non-charge transport material may be selected from well-known materials.
[0231] The protective layer may contain other well-known additives.
[0232] The formation of the protective layer is not particularly limited, and a well-known formation method can be used. For example, the protective layer can be formed by forming a coating film of a coating liquid for forming the protective layer in which the above components are added to a solvent, drying the coating film, and, if necessary, subjecting it to a curing treatment such as heating.
[0233] Examples of solvents for preparing a coating solution for forming a protective layer include aromatic solvents such as toluene and xylene, ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone and cyclohexanone, ester solvents such as ethyl acetate and butyl acetate, ether solvents such as tetrahydrofuran and dioxane, cellosolve solvents such as ethylene glycol monomethyl ether, and alcohol solvents such as isopropyl alcohol and butanol. These solvents may be used alone or in combination of two or more. The protective layer-forming coating liquid may be a solvent-free coating liquid.
[0234] Examples of a method for applying the protective layer-forming coating liquid onto a photosensitive layer (e.g., a charge transport layer) include conventional methods such as dip coating, push-up coating, wire bar coating, spray coating, blade coating, knife coating, and curtain coating.
[0235] The thickness of the protective layer is set, for example, preferably in the range of 1 μm or more and 20 μm or less, and more preferably in the range of 2 μm or more and 10 μm or less.
[0236] (single-layer photosensitive layer) The single-layer type photosensitive layer (charge generation / charge transport layer) is, for example, a layer containing a charge generation material, a charge transport material, and, if necessary, a binder resin and other well-known additives. Note that these materials are the same as those described for the charge generation layer and the charge transport layer. The content of the charge generating material in the single-layer photosensitive layer is preferably 0.1% by mass to 10% by mass, more preferably 0.8% by mass to 5% by mass, based on the total solid content. The content of the charge transport material in the single-layer photosensitive layer is preferably 5% by mass to 50% by mass, based on the total solid content. The method for forming the single-layer type photosensitive layer is the same as the method for forming the charge generating layer and the charge transport layer. The thickness of the single-layer photosensitive layer is, for example, 5 μm or more and 50 μm or less, and preferably 10 μm or more and 40 μm or less.
[0237] [Configuration of image forming apparatus (and process cartridge)] The image forming apparatus according to this embodiment includes an image holder, a charging means for charging the surface of the image holder, an electrostatic image forming means for forming an electrostatic image on the surface of the charged image holder, a developing means that contains an electrostatic image developer containing a toner having toner particles and develops the electrostatic image formed on the surface of the image holder by the electrostatic image developer as a toner image, a transfer means that transfers the toner image formed on the surface of the image holder to the surface of a recording medium, and a cleaning device having a cleaning blade that contacts and cleans the outer peripheral surface of the image holder.
[0238] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as an apparatus equipped with a transfer means for transferring a toner image on an image holder onto a recording medium via a secondary transfer body (e.g., a secondary transfer belt); an apparatus equipped with a fixing means for fixing the toner image transferred onto the surface of the recording medium; an apparatus equipped with a cleaning device for cleaning the surface of the image holder before charging after the toner image is transferred; an apparatus equipped with a static elimination device for irradiating the surface of the image holder with static elimination light to eliminate static electricity before charging after the toner image is transferred; and an apparatus equipped with an image holder heating member for increasing the temperature of the image holder and reducing the relative temperature.
[0239] The image forming apparatus according to the present embodiment may be either a dry development type image forming apparatus or a wet development type image forming apparatus (a development type using a liquid developer).
[0240] In the image forming apparatus according to the present embodiment, for example, the portion including the image carrier may be a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge including a toner image forming device and a transfer device is preferably used.
[0241] (Image forming method) The image forming method according to this embodiment includes a charging step of charging the surface of an image holder, an electrostatic image forming step of forming an electrostatic image on the charged surface of the image holder, a developing step of developing the electrostatic image formed on the surface of the image holder as a toner image using an electrostatic image developer containing a toner having toner particles, a transfer step of transferring the toner image formed on the surface of the image holder to the surface of a recording medium, and a cleaning step of contacting a cleaning blade with the outer peripheral surface of the image holder to clean it. The toner particles have a releasing agent present within 800 nm from the surface that accounts for 70% or more of the releasing agent in the entire toner particle, and the melting temperature of the releasing agent is 65° C. or more and 80° C. or less. The cleaning blade is made of polyurethane resin. The total amount of F and Si present within 200 nm from the surface that contacts the image carrier accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface.
[0242] Hereinafter, an example of an image forming apparatus and an image forming method according to the present embodiment will be described with reference to the drawings. However, the image forming apparatus and the image forming method according to the present embodiment are not limited to this. Note that the main parts shown in the drawings will be described, and the description of the rest will be omitted.
[0243] FIG. 2 is a schematic diagram showing an example of the image forming apparatus according to the present embodiment. As shown in FIG. 2, the image forming apparatus 100 according to the present embodiment includes a process cartridge 300 including an electrophotographic photoreceptor 7 (an example of an image carrier), an exposure device 9 (an example of an electrostatic latent image forming means), a transfer device 40 (a primary transfer device), and an intermediate transfer body 50. In the image forming apparatus 100, the exposure device 9 is disposed at a position where it can expose the electrophotographic photoreceptor 7 from the opening of the process cartridge 300, the transfer device 40 is disposed at a position facing the electrophotographic photoreceptor 7 via the intermediate transfer body 50, and the intermediate transfer body 50 is disposed with a part of it in contact with the electrophotographic photoreceptor 7. Although not shown, the image forming apparatus 100 also includes a secondary transfer device that transfers the toner image transferred to the intermediate transfer body 50 to a recording medium (e.g., paper). The intermediate transfer body 50, the transfer device 40 (a primary transfer device), and the secondary transfer device (not shown) correspond to an example of a transfer means.
[0244] 2 supports an electrophotographic photoreceptor 7, a charging device 8 (an example of a charging means), a developing device 11 (an example of a developing means), and a cleaning device 13 integrally within a housing. The cleaning device 13 has a cleaning blade 131, and the cleaning blade 131 is disposed so as to come into contact with the surface of the electrophotographic photoreceptor 7. Note that the cleaning member may not be in the form of the cleaning blade 131, but may be a conductive or insulating fibrous member, which may be used alone or in combination with the cleaning blade 131.
[0245] FIG. 2 shows an example of an image forming apparatus equipped with a fibrous member 132 (roll-shaped) that supplies lubricant 14 to the surface of electrophotographic photosensitive member 7, and a fibrous member 133 (flat brush-shaped) that assists in cleaning, which may be arranged as needed.
[0246] Hereinafter, each configuration of the image forming apparatus according to this embodiment will be described.
[0247] -Charging device- As the charging device 8, for example, a contact type charger using a conductive or semiconductive charging roller, charging brush, charging film, charging rubber blade, charging tube, etc. Also, a non-contact type roller charger, a scorotron charger or corotron charger that utilizes corona discharge, or other chargers known per se, can be used.
[0248] -Exposure equipment- The exposure device 9 may be, for example, an optical device that exposes the surface of the electrophotographic photoreceptor 7 with light such as semiconductor laser light, LED light, or liquid crystal shutter light in a predetermined image. The wavelength of the light source is within the spectral sensitivity range of the electrophotographic photoreceptor. The wavelength of the semiconductor laser is mainly near infrared light having an oscillation wavelength of about 780 nm. However, it is not limited to this wavelength, and a laser having an oscillation wavelength of 600 nm or a blue laser having an oscillation wavelength of 400 nm to 450 nm may also be used. In addition, a surface-emitting laser light source capable of outputting multiple beams is also effective for forming a color image.
[0249] -Developing device- The developing device 11 may be, for example, a general developing device that develops by contacting or non-contacting a developer. The developing device 11 is not particularly limited as long as it has the above-mentioned functions, and may be selected according to the purpose. For example, it may be a known developing device that has a function of attaching a one-component developer or a two-component developer to the electrophotographic photoreceptor 7 using a brush, roller, or the like. Among them, it is preferable to use a developing roller that holds a developer on its surface.
[0250] The developer used in the developing device 11 may be a one-component developer containing only toner, or may be a two-component developer containing toner and a carrier. The developer may be magnetic or non-magnetic. Well-known developers are used.
[0251] -Cleaning device- The cleaning device 13 is a cleaning blade type device equipped with a cleaning blade 131 .
[0252] -Transfer device- Examples of the transfer device 40 include known transfer chargers such as a contact type transfer charger using a belt, roller, film, rubber blade, etc., and a scorotron transfer charger or corotron transfer charger that utilizes corona discharge.
[0253] -Intermediate transfer body- A belt-like intermediate transfer belt containing semiconductive polyimide, polyamideimide, polycarbonate, polyarylate, polyester, rubber, etc. is used as the intermediate transfer body 50. The intermediate transfer body may be in the form of a drum other than a belt.
[0254] FIG. 3 is a schematic diagram showing another example of the image forming apparatus according to the present embodiment. 3 is a tandem-type multi-color image forming apparatus equipped with four process cartridges 300. In the image forming apparatus 120, the four process cartridges 300 are arranged in parallel on the intermediate transfer body 50, and one electrophotographic photosensitive body is used for each color. The image forming apparatus 120 has the same configuration as the image forming apparatus 100, except that it is a tandem type.
[0255] Although the present embodiment has been described above, the present invention is not limited to the above embodiment, and various modifications, changes, and improvements are possible. EXAMPLES
[0256] Hereinafter, examples of the present disclosure will be described, but the present disclosure is not limited to the following examples. In the following description, unless otherwise specified, all "parts" and "%" are based on mass.
[0257] Example 1 <Preparation of electrostatic image developer> -Preparation of amorphous polyester resin dispersion- (Preparation of polyester resin dispersion (APE1)) Terephthalic acid: 30 parts by mole Fumaric acid: 70 parts by mole Bisphenol A ethylene oxide adduct: 5 parts by mole Bisphenol A propylene oxide adduct: 95 parts by mole The above materials were charged into a 5-liter flask equipped with a stirrer, nitrogen inlet tube, temperature sensor, and distillation column, and the temperature was raised to 210°C over 1 hour, and 1 part of titanium tetraethoxide was added for 100 parts of the above materials. The temperature was raised to 230°C over 0.5 hours while distilling off the generated water, and the dehydration condensation reaction was continued at that temperature for 1 hour, after which the reactant was cooled. In this way, a polyester resin with a weight average molecular weight of 18,500, an acid value of 14 mgKOH / g, and a glass transition temperature of 59°C was synthesized.
[0258] 40 parts of ethyl acetate and 25 parts of 2-butanol were added to a vessel equipped with a temperature control means and a nitrogen replacement means to prepare a mixed solvent, after which 100 parts of polyester resin were gradually added and dissolved, and a 10% by mass aqueous ammonia solution (equivalent to 3 times the molar amount of the acid value of the resin) was added thereto and stirred for 30 minutes. Next, the inside of the container was replaced with dry nitrogen, the temperature was kept at 40°C, and 400 parts of ion-exchanged water was dropped at a rate of 2 parts / min while stirring the mixture, to perform emulsification. After the dropwise addition was completed, the emulsion was returned to room temperature (20°C to 25°C), and dry nitrogen was bubbled for 48 hours while stirring to reduce ethyl acetate and 2-butanol to 1,000 ppm or less, and a resin particle dispersion in which resin particles having a volume average particle size of 200 nm were dispersed was obtained. Ion-exchanged water was added to the resin particle dispersion to adjust the solid content to 20 mass%, to obtain a polyester resin particle dispersion (APE1).
[0259] -Preparation of colorant particle dispersion- (Preparation of Colorant Particle Dispersion (Black Pigment Dispersion)) Carbon black (Cabot, Regal 330): 250 parts Anionic surfactant (Daiichi Kogyo Seiyaku Co., Ltd., Neogen SC): 33 parts (60% active ingredient, 8% colorant) -Ion-exchanged water: 750 parts 280 parts of ion-exchanged water and 33 parts of anionic surfactant were placed in a stainless steel container of a size such that the height of the liquid surface would be about 1 / 3 of the height of the container when all of the above components were added, and after the surfactant was sufficiently dissolved, all of the solid solution pigment was added and stirred with a stirrer until there was no unwetted pigment, and the mixture was sufficiently defoamed. After defoaming, the remaining ion-exchanged water was added, and the mixture was dispersed for 10 minutes at 5000 rpm using a homogenizer (IKA Ultra Turrax T50), and then defoamed by stirring with a stirrer for 1 day and night. After defoaming, the mixture was dispersed again for 10 minutes at 6000 rpm using a homogenizer, and then defoamed by stirring with a stirrer for 1 day and night. Subsequently, the dispersion was dispersed at a pressure of 240 MPa using a high-pressure impact disperser Ultimizer (Sugino Machine Co., Ltd., HJP30006). Dispersion was performed for 25 passes, calculated from the total amount charged and the processing capacity of the device. The resulting dispersion was left to stand for 72 hours to remove the precipitate, and ion-exchanged water was added to adjust the solid content to 15%, to obtain a colorant particle dispersion. The volume average particle size D50 of the particles in this colorant particle dispersion was 135 nm.
[0260] -Preparation of release agent dispersion- (Preparation of release agent dispersion (WAX1)) Paraffin wax (HNP9 made by Nippon Seiro, melting temperature 75℃): 270 parts Anionic surfactant (Dai-ichi Kogyo Seiyaku Co., Ltd., Neogen RK, active ingredient amount: 60%): 13.5 parts (as an active ingredient, 3.0% relative to the release agent) Ion-exchanged water: 21.6 parts The above components were mixed and the release agent was dissolved in a pressure discharge homogenizer (Gaulin homogenizer, manufactured by Gaulin Co., Ltd.) at an internal liquid temperature of 120°C. The mixture was then dispersed at a dispersion pressure of 5 MPa for 120 minutes, then at 40 MPa for 360 minutes, and cooled to obtain a release agent dispersion (WAX1). The volume average particle size D50 of the particles in this release agent dispersion (WAX1) was 225 nm. Ion-exchanged water was then added to adjust the solid content to 20.0%.
[0261] -Preparation of mixed particle dispersion- (Preparation of mixed particle dispersion (RW1)) 150 parts of polyester resin particle dispersion (APE1), 20 parts of release agent particle dispersion (WAX1), and 2.9 parts of anionic surfactant (Dowfax2A1 manufactured by The Dow Chemical Company) were mixed, and then 1.0% nitric acid was added at a temperature of 25°C to adjust the pH to 3.0, to obtain a mixed particle dispersion (RW1).
[0262] - Toner preparation - Polyester resin particle dispersion (APE1): 700 parts Colorant particle dispersion: 133 parts Ion-exchanged water: 400 parts Anionic surfactant (Dowfax2A1, manufactured by The Dow Chemical Company): 2.9 parts The above components were placed in a 3-liter reaction vessel equipped with a thermometer, a pH meter, and a stirrer, and 1.0% nitric acid was added at 25° C. to adjust the pH to 3.0. The mixture was then dispersed at 5,000 rpm with a homogenizer (Ultra Turrax T50, manufactured by IKA Japan Co., Ltd.) while 130 parts of the prepared aqueous aluminum sulfate solution was added and dispersed for 6 minutes.
[0263] Then, a stirrer and a mantle heater were installed in the reaction vessel, and the rotation speed of the stirrer was adjusted so that the slurry was sufficiently stirred. The temperature was raised at a rate of 0.2°C / min up to 40°C, and at a rate of 0.05°C / min after exceeding 40°C, and the particle size was measured every 10 minutes using a Multisizer II (aperture diameter: 50μm, manufactured by Coulter). When the volume average particle size reached 5.0μm, the temperature was maintained, and 450 parts of the mixed particle dispersion (RW1) were added over 5 minutes. After maintaining for 30 minutes, the pH was adjusted to 9.0 using a 1% aqueous sodium hydroxide solution. Thereafter, the temperature was raised to 90°C at a rate of 1°C / min, and maintained at 98°C, while adjusting the pH to 9.0 in the same manner every 5°C. When the particle shape and surface properties were observed using an optical microscope and a scanning electron microscope (FE-SEM), the coalescence of the particles was confirmed at the 10.0th hour, so the vessel was cooled to 30°C over 5 minutes with cooling water.
[0264] The cooled slurry was passed through a nylon mesh with 15 μm openings to remove coarse powder, and the toner slurry that passed through the mesh was filtered under reduced pressure with an aspirator. The toner remaining on the filter paper was crushed finely by hand and added to ion-exchanged water with a temperature of 30° C. and 10 times the amount of the toner, and mixed and stirred for 30 minutes. The mixture was then filtered under reduced pressure with an aspirator, and the toner remaining on the filter paper was crushed finely by hand and added to ion-exchanged water with a temperature of 30° C. and 10 times the amount of the toner, and mixed and stirred for 30 minutes, and then filtered under reduced pressure with an aspirator again, and the electrical conductivity of the filtrate was measured. This operation was repeated until the electrical conductivity of the filtrate was 10 μS / cm or less, and the toner was washed. The washed toner was crushed finely with a wet-dry type granulator (Comil), and then vacuum-dried in an oven at 35° C. for 36 hours to obtain toner particles.
[0265] Then, 3.3 parts of silica particles were added as an external additive to 100 parts of toner particles. The mixture was then mixed for 3 minutes at a peripheral speed of 30 m / s using a Henschel mixer. The mixture was then sieved using a vibrating sieve with an opening of 45 μm to obtain a toner.
[0266] -Creating the carrier- 500 parts of spherical magnetite particle powder having a volume average particle size of 0.18 μm was put into a Henschel mixer and thoroughly stirred, after which 5 parts of a titanate coupling agent was added, the temperature was raised to 95° C., and the mixture was mixed and stirred for 30 minutes to obtain spherical magnetite particles coated with a titanate coupling agent. Next, 6 parts of phenol, 10 parts of 30% formalin, 500 parts of magnetite particles, 7 parts of 25% aqueous ammonia, and 400 parts of water were added to a 1L four-neck flask and mixed and stirred. Next, the mixture was heated to 90°C over 60 minutes while stirring, reacted at the same temperature for 180 minutes, cooled to 30°C, added with 500ml of water, removed the supernatant, and washed the precipitate with water. This was dried at 180°C under reduced pressure, and coarse powder was removed using a sieve with a mesh size of 106μm to obtain core particles with an average particle size of 38μm. Next, 200 parts of toluene and 35 parts of a styrene-methyl methacrylate copolymer (component molar ratio 10:90, weight average molecular weight 160,000) were stirred with a stirrer for 90 minutes to obtain a coating resin solution. 1000 parts of core particles and 70 parts of coating resin solution were placed in a vacuum degassing kneader coater (rotor-wall clearance 35 mm) and stirred at 30 rpm for 30 minutes while maintaining the temperature at 65°C. The temperature was then lowered to 88°C, and the mixture was depressurized to remove toluene, degass, and dried. The mixture was then passed through a mesh with 75 μm openings. The shape factor SF2 of the carrier was 104.
[0267] - Preparation of developer - A developer was prepared by mixing 8 parts of the toner and 100 parts of the carrier in a V blender.
[0268] - Toner properties - The ratio of the release agent present in the region within 800 nm from the surface of the toner particles to the release agent in the entire toner particles (surface layer ratio of the release agent) was measured by the above-mentioned method. Also, the melting temperature of the release agent was measured by the above-mentioned method.
[0269] <Cleaning Blade Production> 100 parts by mass of polycaprolactone polyol (molecular weight 2000) as a high molecular weight polyol component and 58 parts by mass of 4,4'-diphenylmethane diisocyanate (MDI: manufactured by DIC Corporation) as a polyisocyanate component were reacted at 115°C for 20 minutes. Then, 6.1 parts by mass of 1,4-butanediol and 2.6 parts by mass of trimethylolpropane as low molecular weight polyol components were mixed and heat cured for 40 minutes in a mold maintained at 140°C. After molding, the rubber elastic body was cut into a width of 14 mm, a thickness of 1.9 mm, and a length of 330 mm, and this rubber elastic body was bonded to a support plate to form a blade substrate.
[0270] A surface treatment liquid was obtained by dispersing and mixing 80 parts by mass of ethyl acetate as an organic solvent, 25 parts by mass of 4,4'-diphenylmethane diisocyanate (MDI: "Millionate MT" manufactured by Tosoh Corporation, melting point: 38°C) as an isocyanate compound, and 5 parts by mass of a silicone-modified acrylic polymer (8BS-9000; manufactured by Taisei Fine Chemical Co., Ltd.) as an acrylic polymer having a siloxane bond, which is a specific polymer, in a ball mill for 5 hours.
[0271] The blade substrate was immersed in the surface treatment liquid for 60 seconds while keeping the surface treatment liquid at 23° C., and then dried for 1 minute in a room temperature (25° C.) environment. Next, the surface of the dried blade substrate was wiped with a sponge containing a small amount of toluene, further dried for 1 minute in a 25° C. environment, and heated for 50 minutes in an oven kept at 25° C. to obtain a cleaning blade.
[0272] -Cleaning blade properties- The ratio of the total amount of F and Si present within 200 nm of the surface in contact with the image carrier to the total amount of F and Si present within 5 μm of the surface of the cleaning blade (surface ratio of F, Si), the total amount of F and Si present on the surface in contact with the image carrier (surface F, Si amount (atm %)), the total amount of F and Si present at a position 50 nm from the surface in contact with the image carrier (50 nm position F, Si amount (atm %)), and the 100% modulus (MPa) were measured by the above-mentioned method.
[0273] <Preparation of photoreceptor> As the polyester resin (1), a polyester resin (PE1) composed of 50 mol % of the dicarboxylic acid unit (A2-3) and 50 mol % of the diol unit (B1-4) and having a weight average molecular weight of 50,000 was prepared.
[0274] - Formation of undercoat layer - As a conductive substrate, an aluminum cylindrical tube having an outer diameter of 30 mm, a length of 250 mm, and a wall thickness of 1 mm was prepared.
[0275] Zinc oxide (average particle size 70 nm, specific surface area 15 m 2 100 parts of a silane coupling agent (trade name: KBM603, manufactured by Shin-Etsu Chemical Co., Ltd., N-2-(aminoethyl)-3-aminopropyltrimethoxysilane) was added to the mixture, and 1.3 parts of the silane coupling agent was added to the mixture. After adding the toluene, the mixture was stirred for 2 hours, and then the toluene was distilled off under reduced pressure, followed by baking at 120°C for 3 hours to obtain zinc oxide surface-treated with a silane coupling agent.
[0276] 110 parts of the surface-treated zinc oxide was mixed with 500 parts of tetrahydrofuran by stirring, and a solution of 0.6 parts of alizarin dissolved in 50 parts of tetrahydrofuran was added thereto, followed by stirring for 5 hours at 50° C. Thereafter, the solid content was filtered off by reduced pressure filtration and dried under reduced pressure at 60° C. to obtain zinc oxide with alizarin added thereto.
[0277] 100 parts of a solution of 60 parts of alizarin-added zinc oxide, 13.5 parts of a curing agent (blocked isocyanate, product name: Sumidur 3175, manufactured by Sumitomo Bayern Urethane Co., Ltd.), and 15 parts of butyral resin (product name: S-LEC BM-1, manufactured by Sekisui Chemical Co., Ltd.) dissolved in 68 parts of methyl ethyl ketone was mixed with 5 parts of methyl ethyl ketone, and the mixture was dispersed for 2 hours in a sand mill using glass beads of 1 mm diameter to obtain a dispersion liquid. 0.005 parts of dioctyltin dilaurate as a catalyst and 4 parts of silicone resin particles (product name: Tospearl 145, manufactured by Momentive Performance Materials Co., Ltd.) were added to the dispersion liquid to obtain a coating liquid for forming an undercoat layer. The coating liquid for forming an undercoat layer was applied to the outer peripheral surface of a conductive substrate by a dip coating method, and dried and cured at 170°C for 40 minutes to form an undercoat layer. The average thickness of the undercoat layer was 25 μm.
[0278] - Formation of charge generation layer - A mixture of 15 parts of hydroxygallium phthalocyanine (having diffraction peaks at Bragg angles (2θ±0.2°) of at least 7.5°, 9.9°, 12.5°, 16.3°, 18.6°, 25.1°, and 28.3° in the X-ray diffraction spectrum using Cukα characteristic X-rays) as a charge generating material, 10 parts of vinyl chloride-vinyl acetate copolymer resin (trade name: VMCH, manufactured by Nippon Unicar Co., Ltd.) as a binder resin, and 200 parts of n-butyl acetate was dispersed in a sand mill using glass beads with a diameter of 1 mm for 4 hours. 175 parts of n-butyl acetate and 180 parts of methyl ethyl ketone were added to the dispersion and stirred to obtain a coating solution for forming a charge generating layer. The coating solution for forming a charge generating layer was dip-coated on the undercoat layer and dried at room temperature (25°C±3°C) to form a charge generating layer with an average thickness of 0.18 μm.
[0279] - Formation of charge transport layer - 60 parts of polyester resin (PE1) as a binder resin and 40 parts of CTM-1 as a charge transport material were dissolved in 270 parts of tetrahydrofuran and 30 parts of toluene to obtain a coating liquid for forming a charge transport layer. The coating liquid for forming a charge transport layer was dip-coated on the charge generation layer and dried at 145°C for 30 minutes to form a charge transport layer with an average thickness of 40 μm.
[0280] [ka]
[0281] <Image forming device> The electrostatic image developer, the photoconductor, and the cleaning blade for the photoconductor obtained above were attached to an image forming apparatus "Apeos C-8180 manufactured by FUJIFILM Business Innovation Co., Ltd.".
[0282] [Examples 2 to 19, Comparative Examples 1 to 2] <Preparation of electrostatic image developer> In Example 1, a release agent used in preparing the release agent dispersion was selected, and the amount of the mixed particle dispersion (RW1) used in preparing the toner was adjusted to prepare toner particles that satisfied the "surface layer ratio (%) of the release agent" and "melting temperature (°C) of the release agent" shown in Tables 1 and 2, and an electrostatic image developer was obtained. As the release agents having the melting temperatures shown in Table 1, the following were used alone or in combination. Paraffin wax (manufactured by Nippon Seiro Co., Ltd., melting temperature 64°C) Ester wax (NOF Corp., melting temperature 82°C)
[0283] <Cleaning Blade Production> In Example 1, the amount of 4,4'-diphenylmethane diisocyanate (MDI: "Millionate MT" manufactured by Tosoh Corporation, melting point: 38°C) used in forming the cleaning blade was changed to the amount shown in Table 1. In addition, the composition of the surface treatment liquid used in the surface modification treatment of the contact portion of the obtained blade substrate and the conditions of the surface heat treatment were changed to those shown in Table 1, and a cleaning blade was produced that satisfied the "surface ratio of F,Si (%)", "surface F,Si amount (atm%)", "50 nm position F,Si amount (atm%)", and "100% modulus (MPa)" shown in Table 2. In addition, the pressing pressure NF (gf / mm), pressing angle WA (°), and NF x WA when mounting the obtained cleaning blade on an image forming apparatus were set to the conditions shown in Table 2. The components of the surface treatment solution shown in Table 1 were as follows: Silicone modified acrylic polymer (8BS-9000; Taisei Fine Chemical Co., Ltd.) Fluorosilicone modified acrylic polymer (8FS-009; Taisei Fine Chemical Co., Ltd.) Isocyanate compound (MDI: "Millionate MT" manufactured by Tosoh Corporation, melting point: 38°C)
[0284] <Evaluation test> Using the image forming apparatus prepared in each Example and Comparative Example, 50,000 images with an image density of 0.5% were printed on A4 paper in a normal temperature and low humidity environment (21°C 10%). The image quality and cleaning blade after printing were evaluated according to the following criteria.
[0285] Filming An observed image of the photoreceptor surface of 100 μm square was binarized, the area ratio occupied by the deposits was determined, and the result was evaluated according to the following criteria. -standard- A: Not occurred B: A small amount of additive filming occurred, which was at a level that was fully acceptable for practical use. C: Filming occurred. Permissible level for practical use. D: Filming occurred. Unacceptable level for practical use. E: Filming occurs frequently. Unacceptable level for practical use.
[0286] Blade wear The depth of wear at the contact portion of the cleaning blade was measured by observing the cross-sectional profile with a laser microscope VK-9500 manufactured by Keyence Corporation. -standard- The wear depth of the cleaning blade was measured and evaluated according to the following criteria. A: Wear depth < 0.5μm B: 0.5μm≦wear depth<1.0μm C: 1.0μm≦wear depth<1.5μm D: 1.5μm≦wear depth<2.0μm E: 2.0μm≦wear depth<2.5μm
[0287] [Table 1]
[0288] [Table 2]
[0289] As shown in Tables 1 and 2, the image forming apparatus of this embodiment suppresses the occurrence of toner filming on the photoreceptor surface and suppresses wear on the cleaning blade compared to the comparative example.
[0290] The present embodiment includes the following aspects. (((1))) An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; a developing means for developing an electrostatic image formed on the surface of the image carrier by the electrostatic image developer into a toner image, the developing means containing an electrostatic image developer containing a toner having toner particles, the release agent present in an area within 800 nm from the surface of the toner particles being 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent being 65° C. or more and 80° C. or less; a transfer means for transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a cleaning device having a cleaning blade which comes into contact with and cleans the outer peripheral surface of the image carrier, the cleaning blade being made of polyurethane resin, and the total amount of F and Si present within 200 nm from the surface in contact with the image carrier is 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming apparatus comprising: (((2))) The image forming apparatus according to (((1))), wherein the amount of the release agent present in a region within 800 nm from the surface of the toner particle is 75% or more of the release agent in the entire toner particle. (((3))) The image forming apparatus according to (((1))) or (((2))), wherein the melting temperature of the release agent is 70° C. or higher and 75° C. or lower. (((4))) The image forming apparatus according to any one of (((1))) to (((3))), wherein the 100% modulus at 23° C. of the surface of the cleaning blade that comes into contact with the image carrier is 11 MPa or more and 22 MPa or less. (((5))) The image forming apparatus according to (((4))), wherein the 100% modulus at 23° C. of the surface of the cleaning blade that comes into contact with the image carrier is 15 MPa or more and 18 MPa or less. (((6))) The image forming apparatus of any one of (((1))) to (((5))), wherein the total amount of F and Si present within 200 nm from the surface that contacts the image carrier of the cleaning blade accounts for 85% or more of the total amount of F and Si present within 5 μm from the surface. (((7))) The image forming apparatus according to any one of (((1))) to (((6))), wherein the cleaning blade has a surface that comes into contact with the image carrier in which the total amount of F and Si is 15 atm % or more. (((8))) The image forming apparatus according to (((7))), wherein the cleaning blade has a surface that comes into contact with the image carrier and the total amount of F and Si present thereon is 18 atm % or more and 25 atm % or less. (((9))) The image forming apparatus according to any one of (((1))) to (((8))), wherein the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface that contacts the image carrier of 0.3 atm % or more. (((10))) The image forming apparatus according to (((9))), wherein the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface that contacts the image carrier of 1.0 atm % or more and 2.0 atm % or less. (((11))) The image forming apparatus according to any one of (((1))) to (((10))), wherein the cleaning blade contains a silicone-based polymer in a surface layer that comes into contact with the image carrier. (((12))) The image forming apparatus according to any one of (((1))) to (((11))), wherein the product of the static pressing pressure NF between the cleaning blade and the image carrier and the pressing angle WA is 40 or more and 60 or less. (((13))) a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing, as a toner image, the electrostatic image formed on the surface of the image carrier using an electrostatic image developer containing a toner having toner particles, wherein a release agent present within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a cleaning step of contacting an outer peripheral surface of the image carrier with a cleaning blade made of polyurethane resin, the total amount of F and Si present within 200 nm from the surface in contact with the image carrier being 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming method comprising:
[0291] According to the invention related to (((1))), an image forming apparatus is provided in which the occurrence of toner filming on the surface of an image carrier is suppressed and wear in the cleaning blade is suppressed, compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present within 200 nm from the surface that comes into contact with the image carrier is less than 75% of the total amount of F and Si present within 5 μm from the surface. According to the invention related to (((2))), an image forming apparatus is provided which has excellent low-temperature fixing ability of images compared to an image forming apparatus in which the release agent present in the region within 800 nm from the surface of the toner particle is less than 75% of the release agent in the entire toner particle. According to the invention related to (((3))), an image forming apparatus is provided which is superior in low-temperature image fixing ability compared to an image forming apparatus in which the melting temperature of the release agent is higher than 75°C, and an image forming apparatus is provided in which the occurrence of toner filming on the image carrier surface is suppressed compared to an image forming apparatus in which the melting temperature of the release agent is lower than 70°C. According to the invention related to (((4))) or (((5))), an image forming apparatus is provided in which streak-like image defects caused by localized curling of the blade are suppressed compared to an image forming apparatus in which the 100% modulus at 23°C of the surface of the cleaning blade that contacts the image carrier is less than 11 MPa, and an image forming apparatus is provided in which the occurrence of toner filming on the surface of the image carrier is suppressed compared to an image forming apparatus in which the 100% modulus at 23°C of the surface of the cleaning blade that contacts the image carrier exceeds 22 MPa. According to the invention related to (((6))), there is provided an image forming apparatus in which the occurrence of toner filming on the surface of the image carrier is suppressed and wear of the cleaning blade is suppressed, as compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present within 200 nm from the surface that comes into contact with the image carrier is less than 85% of the total amount of F and Si present within 5 μm from the surface. According to the invention related to (((7))) or (((8))), an image forming apparatus is provided in which the occurrence of toner filming on the surface of the image carrier is suppressed and wear of the cleaning blade is suppressed, as compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present on the surface that contacts the image carrier is less than 15 atm %. According to the invention related to (((9))) or (((10))), there is provided an image forming apparatus in which the occurrence of toner filming on the surface of the image carrier and wear of the cleaning blade are suppressed over time, as compared to an image forming apparatus equipped with a cleaning blade in which the total amount of F and Si present at a position 50 nm from the surface that contacts the image carrier is less than 0.3 atm %. According to the invention pertaining to (((11))), there is provided an image forming apparatus in which the surface layer that comes into contact with the image carrier does not contain a silicone-based polymer, and in which the occurrence of toner filming on the surface of the image carrier is suppressed and wear of the cleaning blade is suppressed, as compared to an image forming apparatus equipped with a cleaning blade that contains a fluorine-based compound. According to the invention pertaining to (((12))), an image forming apparatus is provided in which the occurrence of toner slip-through at the contact point between the image carrier and the cleaning blade is suppressed compared to an image forming apparatus in which the product of the static pressing pressure NF and the pressing angle WA between the cleaning blade and the image carrier is less than 40, and an image forming apparatus is provided in which the occurrence of toner filming on the surface of the image carrier is further suppressed compared to an image forming apparatus in which the product of the pressing pressure NF and the pressing angle WA exceeds 60. According to the invention related to (((13))), there is provided an image forming method in which the occurrence of toner filming on the surface of an image carrier is suppressed and wear of the cleaning blade is suppressed, as compared to an image forming method having a cleaning step using a cleaning blade in which the total amount of F and Si present within 200 nm from the surface in contact with the image carrier is less than 75% of the total amount of F and Si present within 5 μm from the surface. [Explanation of symbols]
[0292] 1 undercoat layer, 2 charge generating layer, 3 charge transport layer, 4 conductive substrate, 7A, 7 electrophotographic photoreceptor, 8 charging device, 9 exposure device, 11 developing device, 13 cleaning device, 14 lubricant, 40 transfer device, 50 intermediate transfer body, 100 image forming apparatus, 120 image forming apparatus, 131 cleaning blade, 132 fibrous member (roll type), 133 fibrous member (flat brush type), 300 process cartridge
Claims
1. An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; a developing means for developing an electrostatic image formed on the surface of the image carrier by the electrostatic image developer into a toner image, the developing means containing an electrostatic image developer containing a toner having toner particles, the release agent present in an area within 800 nm from the surface of the toner particles being 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent being 65° C. or more and 80° C. or less; a transfer means for transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a cleaning device having a cleaning blade which comes into contact with and cleans the outer peripheral surface of the image carrier, the cleaning blade being made of polyurethane resin, and the total amount of F and Si present within 200 nm from the surface in contact with the image carrier is 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming apparatus comprising:
2. 2. The image forming apparatus according to claim 1, wherein the amount of the release agent present in a region within 800 nm from the surface of the toner particle is 75% or more of the release agent in the entire toner particle.
3. 2. The image forming apparatus according to claim 1, wherein the release agent has a melting temperature of 70[deg.] C. or higher and 75[deg.] C. or lower.
4. 2. The image forming apparatus according to claim 1, wherein the 100% modulus at 23[deg.] C. of the surface of the cleaning blade which contacts the image carrier is 11 MPa or more and 22 MPa or less.
5. 5. The image forming apparatus according to claim 4, wherein a 100% modulus at 23[deg.] C. of the surface of said cleaning blade which contacts said image carrier is 15 MPa or more and 18 MPa or less.
6. 2. The image forming apparatus according to claim 1, wherein the total amount of F and Si present within 200 nm from the surface of the cleaning blade that contacts the image carrier accounts for 85% or more of the total amount of F and Si present within 5 μm from the surface.
7. 2. The image forming apparatus according to claim 1, wherein the cleaning blade has a surface contacting the image carrier in which the total amount of F and Si is 15 atm % or more.
8. 8. The image forming apparatus according to claim 7, wherein the cleaning blade has a surface that comes into contact with the image carrier and a total amount of F and Si present thereon is 18 atm % or more and 25 atm % or less.
9. 2. The image forming apparatus according to claim 1, wherein the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface that contacts the image carrier of 0.3 atm % or more.
10. 10. The image forming apparatus according to claim 9, wherein the cleaning blade has a total amount of F and Si present at a position 50 nm from the surface that contacts the image carrier of 1.0 atm % or more and 2.0 atm % or less.
11. The image forming apparatus according to claim 1 , wherein the cleaning blade includes a surface layer that contacts the image carrier and contains a silicone-based polymer.
12. 2. The image forming apparatus according to claim 1, wherein a product of a static pressing pressure NF between said cleaning blade and said image carrier and a pressing angle WA is 40 or more and 60 or less.
13. a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing, as a toner image, the electrostatic image formed on the surface of the image carrier using an electrostatic image developer containing a toner having toner particles, wherein a release agent present in an area within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a cleaning step of contacting an outer peripheral surface of the image carrier with a cleaning blade made of polyurethane resin, the total amount of F and Si present within 200 nm from the surface in contact with the image carrier being 75% or more of the total amount of F and Si present within 5 μm from the surface; An image forming method comprising:
Citation Information
Patent Citations
Cleaning blade, cleaning device, and image forming apparatus
JP2005345493A
Cleaning blade and electrophotographic image forming device using the same
JP2010102327A